Autonomic Computing: Foundations for a New Era in Computing - Manish Parashar; Salim Hariri (Kluwer Academic Publishers, 2015)

CometCloud: Enabling Software-Defined Federations for End-to-End Application Workflows - Javier Diaz-Montes; Moustafa Abdelbaky; Mengsong Zou; Manish Parashar (Internet Computing, IEEE, 2015)

Exploring Data Staging Across Deep Memory Hierarchies for Coupled Data Intensive Simulation Workflows - Tong Jin; Qian Sun; Hoang Bui; Melissa Romanus; Norbert Podhorszki; Scott Klasy; Hermanth Kolla; Jacqueline Chen; Robert Hager; Choong-Seock Chang; Manish Parashar (Proceedings of the 29th IEEE International Parallel & Distributed Processing Symposium, 2015)

Integrating Software Defined Networks within a Cloud Federation - Ioan Petri; Mengsong Zou; Ali Reza Zamani; Javier Diaz-Montes; Omer F. Rana; Manish Parashar (15th International Symposium on Cluster, Cloud and Grid Computing (CCCGrid 2015), 2015)

Market Models for Federated Clouds - Ioan Petri; Javier Diaz-Montes; Mengsong Zou; Tom Beach; Omer Rana; Manish Parashar (IEEE, 2015)

Cloud based Building Data Analytics - Ioan Petri; Omer Rana; Thomas Beach; Mengsong Zou; Javier Diaz-Montes; Manish Parashar; Yacine Rezgui (Proceedings of the Third International Workshop on Data-intensive Process Management in Large-Scale Sensor Systems (DPMSS) & 14th IEEE/ACM International Symposium on Cluster, Cloud and Grid Computing (CCGrid 2014), 2014)

Collaborative Marketplaces for eSciecne: A Medical Imaging Use Case - Mengsong Zou; Javier Diaz-Montes; Ivan Rodero; Manish Parashar; Ioan Peteri; Omer Rana; Xin Qi; David Foran (Proceedings of the Fourth International Workshop on Cloud Services and Web 2.0 Technologies for Collaboration (CSWC 2014), 2014)

Data-driven Workflows in Multi-Cloud Marketplaces - Javier Diaz-Montes; Mengsong Zou; Manish Parashar; Rahul Singh; Shu Tao (Proceedings of the Seventh IEEE International Conference on Cloud Computing (IEEE CLOUD 2014), 2014)

Exploring Energy-Performance-Quality Tradeoffs for Scientific Workflows With In-situ Data Analyses - Georgiana Haldeman; Ivan Rodero; Manish Parashar; Sabela Ramos; Eddy Z. Zhang; Uli Kremer (Proceedings of the Fifth International Conference on Energy-Aware High Performance Computing (EnA-HPC 2014), 2014)

Exploring Models and Mechanisms for Exchanging Resources in a Federated Cloud - Ioan Petri; Thomas Beach; Mengsong Zou; Javier Diaz-Montes; Omer Rana; Manish Parashar (Proceedings of the Second IEEE Conference on Cloud Engineering (IC2E 2014), 2014)

Extending CometCloud to Process Dynamic Data Streams on Heterogeneous Infrastructures - Rafael Tolosana-Calasanz; Javier Diaz-Montes; Omer Rana; Manish Parashar (Proceedings of the International Conference on Cloud and Autonomic Computing (CAC 2014), 2014)

Federating Advanced Cyberinfrastructures with Autonomic Capabilities - Javier Diaz-Montes; Ivan Rodero; Mengsong Zou; Manish Parashar (Cloud Computing for Data-Intensive Applications, 2014)

Flexible I/O Programming API for Big Data Analytics - Norbert Podhorszki; Jeremy Logan; Hasan Abbasi; Jong Choi; Qing Liu; J Mu; Scott Klasky; Manish Parashar; Matthew Wolf (Proceedings of the Fifth International Workshop on Big Data Analytics: Challenges, and Opportunities (BDAC-14) & SC’14, The ACM/IEEE International Conference for High Performance Computing, Networking Storage and Analysis, 2014)

Flexible Scheduling and Control of Bandwidth and In-Transit Services for End-to-End Application Workflows - Mehmet Fatih-Aktas; Georgiana Haldeman; Manish Parashar (Proceedings of the Fourth International Workshop on Network-aware Data Management (NDM) & SC’14, The ACM/IEEE International Conference for High Performance Computing, Networking Storage and Analysis, 2014)

Hello ADIOS: The Challenges and Lessons of Developing Leadership Class I/O Frameworks - Qing Liu; Jeremy Logan; Yuan Tian; Hasan Abbasi; Norbert Podhorszki; Jong Youl Choi; Scott Klasky; Roselyne Tchoua; Jay Lofstead; Ron Oldfield; Manish Parashar; Nagiza Samatova; et al. (Concurrency and Computation: Practice and Experience, 2014)

How Do Nucleosomes Bundle into Chromatin? - Nicholas Clauvelin; Javiar Diaz-Montes; Jaroslaw Zola; Manish Parashar; Wilma K. Olson (2014)

In-transit Data Analysis and Distribution in a Multi-Cloud Environment using CometCloud - Ioan Petri; Omer Rana; Javier Diaz-Montes; Mengsong Zou; Manish Parashar; Thomas Beach; Hua Li; Yacine Rezgui (Proceedings of the International Workshop on Energy Management for Sustainable Internet-of-Things and Cloud Computing (EMSICC'14) & FiCloud 2014, the Second International Conference on Future Internet of Things and Cloud, 2014)

Leveraging Deep Memory Hierarchies for Data Staging in Coupled Data-Intensive Simulation Workflows - Tong Jin; Fan Zhang; Qian Sun; Hoang Bui; Norbert Podhorszki; Scott Klasky; Hemanth Kolla; Jacquline Chen; Robert Hager; Choong-Seock Chang; Manish Parashar (2014)

Online Failure Prediction for HPC Resources Using Decentralized Clustering - Alejandro Pelaez; Andres Quiroz; Edward Chuah; James C. Browne; Manish Parashar (Proceedings of the 21st Annual IEEE International Conference on High Performance Computing (HiPC 2014), 2014)

Online Monitoring of HPC resources using decentralize clustering - Alejandro Pelaez; Manish Parashar; James C. Browne; Andres Quiroz; Edward Chuah (2014)

Preliminary Study of Longitudinal EMR data for Diabetes Forecasting - Vamsi K. Potluru; Javier Diaz-Montes; Vijay Hanagandi; Jaroslaw Zola; Manish Parashar (2014)

Scalable Run-time Data Indexing and Querying for Scientific Simulations - Qian Sun; Tong Jin; Fan Zhang; Hoang Bui; Kesheng Wu; Arie Shoshani; Hermanth Kolla; Scott Klasky; Jacqueline Chen; Manish Parashar (Proceedings of the Fifth International Workshop on Big Data Analytics: Challenges, and Opportunities & SC’14, The ACM/IEEE International Conference for High Performance Computing, Networking Storage and Analysis, 2014)

Seventh International Conference on Contemporary Computing (IC3 2014, 2014)

Working towards Sustainable Scientific Software: Practice and Experiences (WSSSPE) - Daniel Katz; Gabrielle Allen; Neil Chue Hong; Manish Parashar; David Proctor (Proceedings of the International Symposium on Grids and Clouds (ISGC 2014), 2014)

Autonomic Computing on Federated Advanced Cyberinfrastructures - Javier Diaz-Montes; Mengsong Zou; Ivan Rodero; Manish Parashar (2013)

A Case for MapReduce over the Internet - Hrishikesh Gadre; Ivan Rodero; Javier Diaz-Montes; Manish Parashar (Proceedings of ACM International Conference on Cloud and Autonomic Computing (CAC 2013), 2013)

Exploring Online Nuclear Segmentation on Large Fluorescence Brain Tumor Images using CometCloud - Xin Qi; Daihou Wang; Javier Diaz-Montes; Ivan Rodero; Tony Pan; Abulimit Aji; Lee Cooper; Fuyong Xing; Manish Parashar; David J. Foran; Lin Yang (Proceedings of the Sixth International Workshop on High Performance Computing for Biomedical Image Analysis (HPC-MICCAI), 2013)

Exploring Power Behaviors and Tradeoffs of In-situ Data Analytics - Marc Gamell; Ivan Rodero; Manish Parashar; Janine C. Bennett; Hermanth Kolla; Jacqueline Chen; Peer-Timo Bremer; Aaditya Landge; Attila Gyulassy; Valerio Pascucci; Patrick McCormick; Scott Pakin; et al. (Proceedings of SC’13, The ACM/IEEE International Conference for High Performance Computing, Networking Storage and Analysis, 2013)

Federated Computing for the Masses- Tackling Large-scale Engineering Problems - Javier Diaz-Montes; Baskar Ganapathysubramanian; Manish Parashar; Ivan Rodero; Yu Xie; Jaroslaw Zola (The ACM/IEEE International Conference for High Performance Computing, Networking Storage and Analysis, 2013)

High-throughput Content Based Image Retrieval Using GPGPU - Daihou Wang; Xin Qi; Manish Parashar; David J. Foran; Lin Yang (Proceedings of the Sixth International Workshop on High Performance Computing for Biomedical Image Analysis (HPC-MICCAI), 2013)

Outsourcing tasks in CometCloud-based federated systems - Ioan Petri; Tom Beach; Mengsong Zou; Javier Diaz-Montes; Omar Rana; Manish Parashar (6th IEEE/ACM International Conference on Utility and Cloud Computing, 2013)

Proceedings of the 1st Workshop on Energy Efficient High Performance Parallel and Distributed Computing - Ivan Rodero; Manish Parashar (HPDC 2013, 2013)

Proceedings of the 22Nd International Symposium on High-performance Parallel and Distributed Computing - Manish Parashar; Dick Epema; Renato Figueiredo; Jon Weissman (HPDC’13, 2013)

Proceedings of the 7th International Workshop on Virtualization Technologies in Distributed Computing - Frederic Desprez; Adrien Lebre; Manish Parashar (ACM, 2013)

Sixth International Conference on Contemporary Computing (IC3 2013, 2013)

Using Cross-Layer Adaptations for Dynamic Data Management in Large Scale Coupled Scientific Workflows - Tong Jin; Fan Zhang; Qian Sun; Hua Bui; Manish Parashar; Hongfeng Yu; Scott Klasky; Norbert Podhorszki; Hasan Abbasi (Proceedings of SC’13, The ACM/IEEE International Conference for High Performance Computing, Networking Storage and Analysis, 2013)

5th IEEE/ACM International Conference on Utility and Cloud Computing (UCC 2012 Conference Proceedings, 2012)
Keywords: cloud computing

Accelerating MapReduce Analytics Using CometCloud - Moustafa Abdelbaky; Hyunjoo Kim; Ivan Rodero; Manish Parashar (Proceedings of the 5th International Conference on Cloud Computing (IEEE Cloud 2012) -Applications & Experience Track, 2012)

The Analysis of Image Feature Robustness Using CometCloud - Xin Qi; Fuyong Xing; Hyunjoo Kim; Manish Parashar; David Foran; Lin Yang (Journal of Pathology Informatics, Publication of the Association of Pathology Informatics, 2012)

Cloud Paradigms and Practices for Computational and Data-Enabled Science and Engineering - Manish Parashar; M Abdelbaky; I. Rodero; A. Devarakonda (2012)

Combining In-situ and In-transit Processing to Enable Extreme-Scale Scientific Analysis - Janine C. Bennett; Hasan Abbasi; Peer-Timo Bremer; Ray Grout; Attila Gyulass; Tong Jin; Scott Klasky; Hermanth Kolla; Manish Parashar; Valerio Pascucci; Philippe Pebay; David Thompson; et al. (Proceedings of SC’12, The ACM/IEEE International Conference for High Performance Computing, Networking Storage and Analysis, 2012)

Combining In-situ and In-transit Processing to Enable Extreme-Scale Scientific Analysis - J.C. Bennett; H. Abbasi; P-T. Bremer; R. Grout; A. Gyulass; T. Jin; S Klasky; H. Kolla; Manish Parashar; V. Pascucci; P. Pebay; D. Thompson; et al. (Proceedings of SC 2012, The ACM/IEEE International Conference for High Performance Computing, Networking Storage and Analysis, 2012)

Content-based Image Retrieval on Imaged Peripheral Blood Smear Specimens using High Performance Computation - X. Qi; F. Xing; M. Ghadge; I. Rodero; Moustafa Abdelbaky; Manish Parashar; E. Sadimin; D Foran; L. Yang (Proceedings of the Workshop on Data and Compute-Intensive Clinical and Translational Imaging Applications, in conjunction with 15th International Conference on Medical Image Computing and Computer Assisted Intervention (DICTA-MICCAI), 2012)

Content-based Image Retrieval on Imaged Peripheral Blood Smear Specimens using High Performance Computation - Xin Qi; Fuyong Xing; Meghana Ghadge; Ivan Rodero; Moustafa Abdelbaky; Manish Parashar; Evita Sadimin; David Foran; Lin Yang (Proceedings of the Workshop on Data- and Compute-Intensive Clinical and Translational Imaging Applications & 15th International Conference on Medical Image Computing and Computer Assisted Intervention (DICTA-MICCAI), 2012)

Design and Evaluation of Decentralized Online Clustering - A. Quiroz; Manish Parashar (ACM Transactions on Autonomous and Adaptive Systems, 2012)

Distributed Computing Practice for Large-Scale Science & Engineering Applications - Shantenu Jha; Murray Cole; Daniel S. Katz; Manish Parashar; Omer Rana; Jon Weissman (Concurrency and Computation: Practice and Experience, 2012)

Enabling High Performance Computing as a Service - Moustafa Abdelbaky; H. Kim; Manish Parashar; K.E. Jordan; V. Sachdeva; J. Sexton; H. Jamjoom; Z.-Y. Shae; G. Pencheva; R. Tavakoli; M. Wheeler (IEEE Computer, 2012)

Enabling high-performance computing as a service - Moustafa Abdelbaky; Manish Parashar; Hyunjoo Kim; Kirk E. Jordan; Vipin Sachdeva; James Sexton; Hani Jamjoom; Zon-Yin Shae; Gergina Pencheva; Reza Tavakoli; Mary F. Wheeler (Computer, 2012)

Enabling In-situ Execution of Coupled Scientific Workflow on Multi-core Platform - Fan Zhang; Ciprian Docan; Manish Parashar; Scott Klasky; Norbert Podhorszki; Hasan Abbasi (Proceedings of the 26th IEEE International Parallel & Distributed Processing Symposium (IPDPS 2012), 2012)

Energy Efficiency in HPC Systems - Ivan Rodero; Manish Parashar (Energy-Efficient Distributed Computing Systems, Series on Parallel and Distributed Computing, 2012)

Energy-efficient Online Provisioning for HPC Workloads - I. Rodero; A. Quiroz; Manish Parashar; F. Guim; S. Poole (Handbook of Energy-Aware and Green Computing, 2012)

Energy-efficient Thermal-aware Autonomic Management of Virtualized HPC Cloud Infrastructure - I. Rodero; H. Viswanathan; E. K. Lee; M. Gamell; D Pompili; Manish Parashar (Springer Journal of Grid Computing, Special Issue on High Performance Grid and Cloud Computing, 2012)

Exploring Cross-layer Power Management for PGAS Applications on the SCC Platform - M. Gamell; I. Rodero; Manish Parashar; R. Muralidhar (Proceedings of the 21st International ACM Symposium on High-Performance Parallel and Distributed Computing (HPDC"12), 2012)

In-situ Feature-based Objects Tracking for Large-Scale Scientific Simulations - Fan Zhang; Solomon Lasluisa; Tong Jin; Ivan Rodero; Hua Bui; Manish Parashar (Proceedings 2012 International Workshop on Data-Intensive Scalable Computing Systems (DISCS-2012) & SC’12, The ACM/IEEE International Conference for High Performance Computing, Networking Storage and Analysis, 2012)

In-situ Feature-based Objects Tracking for Large-Scale Scientific Simulations - F. Zhang; S. Lasluisa; T. Jin; I. Rodero; H. Bui; Manish Parashar (International Workshop on Data-Intensive Scalable Computing Systems (DISCS), in conjunction with the 2012 ACM/IEEE Supercomputing Conference (SC 2012), 2012)

Leveraging Cloud Federation in a Layered Service Stack Model - D. Villegas; I. Rodero; A. Devarakonda; N. Bobroff; L. Fong; S.M. Sadjadi; Manish Parashar; Y. Liu (Journal of Computer and System Sciences, Special Issue on Cloud Computing, 2012)

Mining Hidden Mixture Context With ADIOS-P To Improve Predictive Pre-fetcher Accuracy - Jong Youl Choi; Hasan Abbasi; David Pugmire; Scott Klasky; Judy Qiu; Geoffrey Fox; Manish Parashar (Proceedings of the Eighth International Conference on eScience (eScience 2012), 2012)

Proceedings of the 41st International Conference on Parallel Processing - Manish Parashar (ICPP 2012, 2012)

Proceedings of the 5th International Conference on Contemporary Computing - Manish Parashar; Dinesh Kaushik; Omer Rana; Ravi Samtaney (IC3 2012, 2012)

Proceedings of the 9th IEEE International Conference on Cloud Computing (CLOUD 2012) IEEE Computer Society Press - Louise Moser; Manish Parashar; P Hung (CLOUD 2012, 2012)

Proceedings of the 9th International Conference on Autonomic and Trusted Computing - Tadashi Dohi; Manish Parashar; Bernady O. Apduhan; Kenji Ishida; K Wolter (ATC 2012, 2012)

A Scalable Messaging System for Accelerating Discovery from Large Scale Scientific Simulations - Tong Jin; Fan Zhang; Manish Parashar; Scott Klasky; Norbert Podhorszki; Hasan Abbasi (Proceedings of 19th Annual International Conference on High Performance Computing (HiPC 2012), 2012)

Understanding I/O Performance using I/O Skeletal Applications - Jeremy Logan; Scott Klasky; Hasan Abbasi; Qing Liu; George Ostrouchov; Manish Parashar; Norbert Podhorszki; Yuan Tian; Matthew Wolf (Proceedings of the Euro-Par 2012 Conference, 2012)

Adaptive Memory Power Management Techniques for HPC Workloads - Karthik Elangovan; Ivan Rodero; Manish Parashar; Francesc Guim; Hernandez. (Proceedings of the 18th IEEE International Conference on High Performance Computing (HiPC) 2011, 2011)

Addressing the Petascale Data Challenge using In-Situ Analytics - Manish Parashar (2011)

The analysis of image texture feature robustness using CometCloud - X. Qi; H. Kim; F. Xing; Manish Parashar; D Foran; L. Yang (Proceedings of the 14th International Conference on Medical Image Computing and Computer Assisted Intervention (MICCAI), 2011)

Autonomic Management of Application Workflow on Hybrid Computing Infrastructure - H. Kim; Y. el-Khamra; I. Rodero; S. Jha; Manish Parashar (Scientific Programming Journal, 2011)

Autonomic Workflow Management in Dynamically Federated, Hybrid Cloud Infrastructures using CometCloud - H. Kim; Manish Parashar; A. Quiroz; N. Gnanasambandam (Cloud Computing: Methodology, Systems, and Applications, 2011)

CometCloud: An Autonomic Cloud Engine - Hyunjoo Kim; Manish Parashar; Rajkumar Buyya; James Broberg; Andrzej Goscinski (Cloud Computing: Principles and Paradigms, 2011)

Dynamic Decision and Data-Driven Strategies for the Optimal Management of Subsurface Geo-systems - Manish Parashar; H. Klie; T. Kurc; U. Catalyurek; J. Saltz; M. F. Wheeler (Journal of Algorithms & Computational Technology, 2011)

Enabling Multi-Physics Coupled Simulations within the PGAS Programming Framework - F. Zhang; C. Docan; Manish Parashar; S Klasky (Proceedings of the 11th IEEE/ACM International Symposium on Cluster, Cloud, and Grid Computing (CCGrid 2011), 2011)

Energy-Aware Application-Centric VM Allocation for HPC Workloads - H. Viswanathan; E. K. Lee; I. Rodero; D Pompili; Manish Parashar; M. Gamell (Proceedings of the Workshop on High-Performance Grid and Cloud Computing, a workshop at the 25th IEEE International Parallel & Distributed Processing Symposium (IPDPS 2011), 2011)
Virtualized datacenters and clouds are being increasingly considered for traditional High-Performance Computing (HPC) workloads that have typically targeted Grids and conventional HPC platforms. However, maximizing energy efficiency, cost-effectiveness, and utilization of datacenter resources while ensuring performance and other Quality of Service (QoS) guarantees for HPC applications requires careful consideration of important and extremely challenging tradeoffs. An innovative application-centric energy-aware strategy for Virtual Machine (VM) allocation is presented. The proposed strategy ensures high resource utilization and energy efficiency through VM consolidation while satisfying application QoS. While existing VM allocation solutions are aimed at satisfying only the resource utilization requirements of applications along only one dimension (CPU utilization), the proposed approach is more generic as it employs knowledge obtained through application profiling along multiple dimensions. The results of our evaluation show that the proposed VM allocation strategy enables significant reduction either in energy consumption or in execution time, depending on the optimization goals.

Examples of In Transit Visualization - Kenneth Moreland; Ron Oldfield; Pat Marion; Sebastien Jourdain; Norbert Podhorszki; Ciprian Docan; Manish Parashar; Mark Hereld; Michael E. Papka; Scott Klasky (Proceedings of the Workshop on Petascale Data Analytics: Challenges and Opportunities (PDAC-11), in conjunction with ACM/IEEE SC11, 2011)

Exploring the Use of Hybrid HPC-Grids/Clouds Infrastructure for Science and Engineering - H. Kim; Y. el-Khamra; S. Jha; Manish Parashar (Cloud Computing: Methodology, Systems, and Applications, 2011)

High Throughput Landmark Based Image Registration Using Cloud Computing - L. Yang; H. Kim; Manish Parashar; D Foran (14th International Conference on Medical Image Computing and Computer Assisted Intervention (MICCAI), 2011)

In situ data processing for extreme scale computing - S Klasky; H. Abbasi; J. Logan; Manish Parashar; K. Schwan; A. Shoshani; M. Wolf; S. Ahern; I. Altintas; W. Bethel; L. Chacon; C.S. Chang; et al. (SciDAC Conference, 2011)

Moving the Code to the Data -- Dynamic Code Deployment using ActiveSpaces - C. Docan; Manish Parashar; J. Cummings; S Klasky (Proceedings of the 25th IEEE International Parallel and Distributed Processing Symposium (IPDPS'11), 2011)

Mptrace: Characterizing Physical Memory Usage for Chip Multiprocessors - Francesc Guim; Miguel Ferrer; Joseph Jorba; Ivan Rodero; Manish Parashar (Proceedings of The First International Conference on Advanced Communications and Computation (INFOCOMP), 2011)

NSF/IEEE-TCPP curriculum initiative on parallel and distributed computing: core topics for undergraduates - S.K. Prasad; A. Chtchelkanova; S. Das; F. Dehne; M. Gouda; A. Gupta; J. Jaja; K. Kant; A. La Selle; R. LeBlanc; A. Lumsdaine; D. Padua; et al. (In Proceedings of the 42nd ACM technical symposium on Computer science education (SIGCSE "11), 2011)

Peer-to-Peer Cloud Provisioning: Service Discovery and Load-Balancing - Rajiv Ranjan; Liang Zhao; Xiaomin Wu; Andres Quiroz; Manish Parashar; Anna Liu; Nikos Antonopoulos; Lee Gillam (Cloud Computing: Principles, Systems and Applications, 2011)

Proceedings of the 18th IEEE International Conference on High Performance Computing - Louise Moser; Manish Parashar; P Hung (HiPC 2011, 2011)

Proceedings of the 4th International Conference on Contemporary Computing - Umit V Catalyurek; Devdatt Dubhashi; Phillip H. Jones; Manish Parashar; B. Schmidt; S. Aluru; S. Bandyopadhyay (Springer, 2011)

Proceedings of the 8th IEEE International COnference on Cloud Computing - Ling Liu; Manish Parashar (CLOUD 2011, 2011)

Skel: Generative Software for Producing Skeletal I/O Applications - Jeremy Logan; Scott Klasky; Jay Lofstead; Hasan Abbasi; Stephane Ethier; Ray Grout; Seung-Hoe Ku; Qing Liu; Xiaosong Ma; Manish Parashar; Norbert Podhorszki; Karsten Schwan; et al. (Proceedings of the Workshop on D3Science, in conjunction with 7th IEEE International Conference on e-Science (e-Science 2011), 2011)

Study of ELM Perturbation Effects on Divertor Heat Loads using Tightly Coupled Kinetic-MHD Simulations - Julian C. Cummings; Choong-Seock Chang; Ciprian Docan; Scott Klasky; Manish Parashar; Gunyoung Park; Norbert Podhorszki; Linda Sugiyama (2011)

Survey and Analysis of Production Distributed Computing Infrastructures - D. S. Katz; S. Jha; Manish Parashar; O. Rana; J. Weissman (Technical Report CI-TR-7-0811. Computation Institute, University of Chicago and Argonne National Laboratory, 2011)

Autonomic Communication - A. V. Vasilakos; Manish Parashar; S. Karnouskos; W. Pedrycz (2010)

Autonomic Management of Distributed Systems using Online Clustering - A. Quiroz; Manish Parashar; I. Rodero (6th Workshop on System Management Techniques, Processes, and Services (SMTPS), 24th IEEE International Parallel and Distributed Processing Symposium (IPDPS 2010), 2010)

Autonomic Policy Adaptation using Decentralized On Clustering - A. Quiroz; Manish Parashar; N. Gnanasambandam; N. Sharma (Proceedings of the 7th IEEE International Conference on Autonomic Computing (ICAC 2010) - Industry Track, 2010)

Bio-inspired Communications for Coordination among Autonomous Underwater Vehicles - B. Chen; D Pompili; Manish Parashar (Proceedings of the 33rd IEEE Sarnoff Symposium, 2010)
To take measurements in space and time from the undersampled vast ocean, it is necessary to employ multiple autonomous underwater vehicles, such as gliders, that communicate and coordinate with each other. These vehicles need to form a team in a specific formation, steer through the 3D region of interest, and take application-dependent measurements such as temperature and salinity. In this paper, bio-inspired underwater acoustic communication and coordination algorithms are proposed to enable glider swarming that is robust against acoustic channel impairments. Performance of the proposed algorithms is evaluated when i) number of vehicles, ii) team formation geometry, and iii) team target trajectory are provided.

Cooperative Detection and Protection against Network Attacks Using Decentralized Information Sharing - G. Zhang; Manish Parashar (Cluster Computing: The Journal of Networks, Software Tools, and Applications, 2010)

DADS: A Dynamic and Adaptive Data Space for Interacting Parallel Applications - F. Zhang; C. Docan; Manish Parashar; S Klasky (Proceedings of the IASTED International Conference on Parallel and Distributed Computing and Systems (PDCD 2010), 2010)

DataSpaces: An Interaction and Coordination Framework for Coupled Simulation Workflows - Manish Parashar; S Klasky; C. Docan (Proceedings of the 19th ACM International Symposium on High Performance Distributed Computing (HPDC 2010), 2010)

EFFIS: an End-to-end Framework for Fusion Integrated Simulation - J. Cummings; A. Sim; A.J. Shoshani; Jay Lofstead; K. Schwan; C. Docan; Manish Parashar; S Klasky; N. Podhorszki; R. Barreto (Proceedings of PDP 2010 - The 18th Euromicro International Conference on Parallel, Distributed and Network-Based Computing, Special session Grid and High Performance Computing for Nuclear Fusion Applications, 2010)

Enabling GPU and Many-Core Systems in Heterogeneous HPC Environments using Memory Considerations - F. Guim; J. Corbalan; I. Rodero; Manish Parashar (Proceedings of the 12th IEEE International Conference on High Performance Computing and Communications (IEEE HPCC 2010), 2010)

Enabling Large-Scale Computational Science: Motivations, Requirements and Challenges - Manish Parashar; Xiaolin Li; Manish Parashar; Xiaolin Li; Sumir Chandra (Advanced Computational Infrastructures for Parallel and Distributed Applications, 2010)

Energy-Aware Online Provisioning for Virtualized Clouds and Data Centers - I. Rodero; J. Jaramillo; A. Quiroz; Manish Parashar; F. Guim (Short Paper, Proceedings of the 19th ACM International Symposium on High Performance Distributed Computing (HPDC 2010), 2010)

Energy-Efficient Application-Aware Online Provisioning for Virtualized Clouds and Data Centers - I. Rodero; J. Jaramillo; A. Quiroz; Manish Parashar; F. Guim; S. Poole (Proceedings of the 1st IEEE International Green Computing Conference (IGCC 2010), 2010)

Experiments with Memory-to-Memory Coupling for End-to-End Fusion Simulation Workflows - C. Docan; Manish Parashar; J. Cummings; N. Podhorszki; S Klasky (Proceedings of the 10th IEEE/ACM International Symposium on Cluster, Cloud and Grid Computing, 2010)

Exploiting VM Technologies for Reactive Thermal Management in Instrumented Datacenters - I. Rodero; E. K. Lee; D Pompili; Manish Parashar; M. Gamell; R.J. Figueiredo (Energy Efficient Grids, Clouds and Clusters (E2GC2) Workshop in conjunction with IEEE Grid 2010, 2010)

Exploring Adaptation to Support Dynamic Applications on Hybrid Grids-Clouds Infrastructure - H. Kim; Y. el-Khamra; S. Jha; Manish Parashar (Proceedings of the 1st Workshop on Scientific Cloud Computing (ScienceCloud 2010), co-located with the 19th ACM International Symposium on High Performance Distributed Computing (HPDC 2010), 2010)

Exploring the Performance Fluctuations of HPC Workloads on Clouds - Y. el-Khamra; H. Kim; S. Jha; Manish Parashar (Proceedings of the 2nd IEEE International Conference on Cloud Computing Technology and Science (CloudCom 2010), 2010)

GrACE: Grid Adaptive Computational Engine for Parallel Structured AMR Applications - Manish Parashar; Xiaolin Li; Manish Parashar; Xiaolin Li; Sumir Chandra (Advanced Computational Infrastructures for Parallel and Distributed Applications, 2010)

HRMS: Hybrid Runtime Management Strategies for Large Scale Parallel Adaptive Applications - Manish Parashar; Xiaolin Li (Advanced Computational Infrastructures for Parallel and Distributed Applications, 2010)

Investigating the Potential of Application-Centric Aggressive Power Management for HPC Workloads - I. Rodero; S. Chandra; Manish Parashar; R. Muralidhar; H. Seshadri; S. Poole (Proceedings of 17th Annual International Conference on High Performance Computing (HiPC 2010), 2010)

Object-Oriented Stream Programming using Aspects - M. Wang; Manish Parashar (Proceedings of the 24th IEEE International Parallel and Distributed Processing Symposium, 2010)

PreDatA - Preparatory Data Analytics on Peta-Scale Machines - F. Zheng; Hasan Abbasi; C. Docan; J. Lofstead; S Klasky; Q. Liu; Manish Parashar; N. Podhorszki; K. Schwan; M. Wolf (Proceedings of the 24th IEEE International Parallel and Distributed Processing Symposium, 2010)

Proactive Thermal Management in Green Datacenters - E. K. Lee; I. Kulkarni; D Pompili; Manish Parashar (Journal of Supercomputing, Special Issue on Energy-Efficient High-Performance Parallel and Distributed Computing, 2010)
The increasing demand for faster computing and high storage capacity has resulted in an increase in energy consumption and heat generation in datacenters. Because of the increase in heat generation, cooling requirements have become a critical concern, both in terms of growing operating costs as well as their environmental and societal impacts. Presently, thermal management techniques make an effort to thermally profile and control datacenters’ cooling equipment to increase their efficiency. In conventional thermal management techniques, cooling systems are triggered by the temperature crossing predefined thresholds. Such reactive approaches result in delayed response as the temperature may already be too high, which can result in performance degradation of hardware. In this work, a proactive control approach is proposed that jointly optimizes the air conditioner compressor duty cycle and fan speed to prevent heat imbalance—the difference between the heat generated and extracted from a machine—thus minimizing the cost of cooling. The proposed proactive optimization framework has two objectives: (i) minimize the energy consumption of the cooling system, and (ii) minimize the risk of equipment damage due to overheating. Through thorough simulations comparing the proposed proactive heat-imbalance estimation-based approach against conventional reactive temperature-based schemes, the superiority of the proposed approach is highlighted in terms of cooling energy, response time, and equipment failure risk.

Proceedings for the 10th IEEE/ACM International Conference on Cluster, Cloud, and Grid Computing - Manish Parashar; Rajkumar Buyya (IEEE, 2010)

Proceedings of the 10th IEEE/ACM International Conference on Cluster, Cloud, and Grid Computing - Manish Parashar; Rajkumar Buyya (IEEE, 2010)

Proceedings of the 17th IEEE International Conference on High Performance Computing - Franck Cappello; Manish Parashar; Rajeev Muralidhar; Viktor K. Prasanna (HiPC 2010, 2010)

Proceedings of the 7th IEEE International Conference on Autonomic Computing and Communications - Emre Kiciman; Manish Parashar (ACM Press, 2010)

A Programming System for Sensor-based Scientific Applications - N. Jiang; Manish Parashar (Journal of Computational Science, 2010)

The Role of Grid Computing Technologies in Cloud Computing - David Villegas; Ivan Rodero; Liana Fong; Norman Bobroff; Yanbin Liu; Manish Parashar; S. Masoud Sadjadi (Handbook of Cloud Computing, 2010)

The Seine Data Coupling Framework for Parallel Scientific Applications - Li Zhang; Ciprian Docan; Manish Parashar (Advanced Computational Infrastructures for Parallel and Distributed Applications, 2010)

Self-adaptive architectures for autonomic computational science - Shantenu Jha; Manish Parashar; Omer Rana; Danny Weyns; Sam Malek; Rogerio De Lemos; Jesper Andersson (Self-Organizing Architectures, 2010)

Towards Energy-Aware Autonomic Provisioning for Virtualized Environments - I. Rodero; J. Jaramillo; A. Quiroz; Manish Parashar; F. Guim (19th ACM International Symposium on High Performance Distributed Computing (HPDC), 2010)

Towards Energy-Efficient Reactive Thermal Management in Instrumented Datacenters - I. Rodero; E. K. Lee; D Pompili; Manish Parashar; M. Gamell; R.J. Figueiredo (Proceedings of the Energy Efficient Grids, Clouds and Clusters Workshop (E2GC2 2010), in conjunction with the IEEE Grid 2010 Conference (Grid 2010), 2010)
Virtual Machine (VM) migration is one of the most common techniques used to alleviate thermal anomalies (i.e., hotspots) in cloud datacenter’s servers of by reducing the load and, therefore, decreasing the server utilization. However, there are other techniques such as voltage scaling that also can be applied to reduce the temperature of the servers in datacenters. Because no single technique is the most efficient to meet temperature/ performance optimization goals in all situations, we work towards an autonomic approach that performs energy-efficient thermal management while ensuring the Quality of Service (QoS) delivered to the users. In this paper, we explore ways to take actions to reduce energy consumption at the server side before performing costly migrations of VMs. Specifically, we focus on exploiting VM Monitor (VMM) configurations, such as pinning techniques in Xen platforms, which are complementary to other techniques at the physical server layer such as using low power modes. To support the arguments of our approach, we present the results obtained from an experimental evaluation on real hardware using High Performance Computing (HPC) workloads on different scenarios.

Towards Energy-Efficient Reactive Thermal Management in Instrumented Datacenters - I. Rodero; E.K Lee; Dario Pompili; Manish Parashar; M. Gamell; R. J. Figueiredo (Proc. of IEEE/ACM International Conference on Energy Efficient Grids, Clouds and Clusters Workshop (E2GC2), 2010)

Advanced Computational Infrastructures for Parallel and Distributed Applications - Manish Parashar; S. Chandra; X. Li (John Wiley and Sons, 2009)

Advanced Risk Analytics on the Cell Broadband Engine - C. Docan; Manish Parashar; C. Marty (2nd International Workshop on Parallel and Distributed Computing in Finance (PDCoF), in conjunction with the 23rd IEEE International Parallel and Distributed Processing Symposium (IPDPS 2009), 2009)

...And eat it too: High read performance in write-optimized HPC I/O middleware file formats - M. Polte; J. Lofstead; J. Bent; G. Gibson; S Klasky; Q. Liu; Manish Parashar; K. Schwan; M. Wolf (Proceedings of the 4th Petascale Data Storage Workshop, in conjunction with Supercomputing 2009, 2009)

ASGrid: Autonomic Management of Hybrid Sensor Grid Systems and Applications - X. Li; X. Liu; H. Zhao; H. Zhao; N. Jiang; Manish Parashar (International Journal of Sensor Networks (IJSNet), 2009)

An Autonomic Approach to Integrated HPC Grid and Cloud Usage - H. Kim; Y. el-Khamra; S. Jha; Manish Parashar (Proceedings of 5th IEEE International Conference on e-Science (e-Science 2009), 2009)

Cost vs. Performance of VaR on Accelerator Platforms - M. Majmudar; C. Docan; Manish Parashar; C. Marty (Proceedings of the Workshop on High Performance Computational Finance (HPCF), in conjunction with Supercomputing 2009 (SC09), 2009)

Critical Perspectives on Large-Scale Distributed Applications and Production Grids - S. Jha; D. Katz; Manish Parashar; O. Rana; J. Weissman (Proceedings of the 10th IEEE/ACM International Conference on Grid Computing (Grid 2009), 2009)

Enabling Autonomic Power-Aware Management of Instrumented Data Centers - N. Jiang; Manish Parashar (5th Workshop on High-Performance, Power-Aware Computing (HPPAC 2009), in conjunction with the 23rd IEEE International Parallel and Distributed Processing Symposium (IPDPS 2009), 2009)

Enabling End-to-end Data-driven Sensor-based Scientific and Engineering Applications - N. Jiang; Manish Parashar (Proceeding of the Workshop on Dynamic Data-Driven Application Systems (DDDAS '09), in conjunction with the International Conference on Computational Science (ICCS 2009), 2009)

High Throughput Data Movement - Scott Klasky; Hasan Abbasi; Viraj Bhat; Ciprian Docan; Steve Hodson; Chen Jin; Jay Lofstead; Manish Parashar; Karsten Schwan; Matthew Wolf (Scientific Data Management: Challenges, Existing Technologies, and Deployment, 2009)

Investigating Autonomic Behaviors in Grid-Based Computational Science Applications - S. Jha; Manish Parashar; O. Rana (Grid Meets Autonomic Computing Workshop (GMAC '09), Proceedings of the 6th International Conference on Autonomic Computing and Communication, 2009)

Investigating the Use of Cloudbursts for High Throughput Medical Image Registration - H. Kim; Manish Parashar; D Foran; L. Yang (Proceedings of the 10th IEEE/ACM International Conference on Grid Computing (Grid 2009), 2009)

Online Risk Analytics on the Cloud - H. Kim; S. Chaudhari; Manish Parashar; C. Marty (Proceedings of the International Workshop on Cloud Computing (Cloud 2009), in conjunction with 9th IEEE/ACM International Symposium on Cluster Computing (CCGrid 2009), 2009)

Pervasive Grids: Challenges and Opportunities - Manish Parashar; J-M. Pierson (Handbook of Research on Scalable Computing Technologies, 2009)

Plasma Fusion Code Coupling using Scalable I/O Services and Scientific Workflows - N. Podhorszki; S Klasky; Q. Liu; C. Docan; Manish Parashar; H. Abbasi; J. Lofstead; K. Schwan; M. Wolf; F. Zheng; J. Cummings (Proceedings of the 4th Workshop on Workflows in Support of Large-Scale Science, in conjunction with Supercomputing 2009 (SC09), 2009)

Proceedings of the 16th IEEE International Conference on High Performance Computing - Yang Yuan; Manish Parashar; Rajeev Muralidhar; Viktor K. Prasanna (HiPC 2009, 2009)

Proceedings of the 6th IEEE International Conference on Autonomic Computing and Communications - Simon Dobson; John Strassner; Manish Parashar; Onn Shehory (ICAC 2009, 2009)

Proceedings of the 6th IEEE International Conference on Autonomic Computing and Communications - Simon Dobson; John Strassner; Manish Parashar; Onn Shehory (ICAC 2009, 2009)

Programming GPU Accelerators with Aspects and Code Transformation - M. Wang; Manish Parashar (Proceedings of the First Workshop on Programming Models for Emerging Architectures (PMEA), Co-located with the 18th International Conference on Parallel Architectures and Compilation Techniques (PACT), 2009)

Robust Clustering Analysis for the Management of Self-Monitoring Distributed Systems - A. Quiroz; N. Gnanasambandam; Manish Parashar; N. Sharma (Cluster Computing: The Journal of Networks, Software Tools, and Applications, Special Issue on Autonomic Computing, 2009)

Self-Adaptive Architectures for Autonomic Computational Science - S. Jha; Manish Parashar; O. Rana (Proceedings of the Self-Organizing Architectures Workshop (SOARS 2009 held in conjunction with Working IEEE/IFIP Conference on Software Architecture (WICSA) and European Conference on Software Architecture (ECSA)), 2009)

Shared Memory Multiprocessors - Liu Zhang; Manish Parashar; Benjamin W. Wah (Wiley Encyclopedia of Computer Science and Engineering, 2009)

Solving Sparse Linear Systems on NVIDIA Tesla GPUs - M. Wang; H. Klie; Manish Parashar; H. Sudan (Proceeding of the Workshop on Using Emerging Parallel Architectures for Computational Science, in conjunction with the International Conference on Computational Science (ICCS 2009), 2009)

Towards Autonomic Workload Provisioning for Enterprise Grids and Clouds - A. Quiroz; H. Kim; Manish Parashar; N. Gnanasambandam; N. Sharma (Proceedings of the 10th IEEE/ACM International Conference on Grid Computing (Grid 2009), 2009)

Adaptive Distributed Mechanisms against Flooding Network Attacks Based on Machine Learning - J. L. Berral; N. Poggi; J. Alonso; R. Gavalda; J. Torres; Manish Parashar (Proceedings of the 1st ACM Workshop on AISec, in conjunction with the 15th ACM Conference on Computer and Communications Security (CCS), 2008)

Adaptive IO System (ADIOS) - C. Jin; S Klasky; S. Hodson; W. Yu; J. Lofstead; H. Abbasi; K. Schwan; M. Wolf; W. Liao; A. Choudhary; Manish Parashar; C. Docan (Cray Users Group (CUG) Workshop, 2008)

Addressing Challenges of Adaptivity and Scale in Parallel Scientific Applications - Manish Parashar (Seminar Series, 2008)

Addressing Challenges of Adaptivity and Scale in Parallel Scientific Applications - Manish Parashar (Seminar Series, 2008)

Asynchronous Replica Exchange for Molecular Simulations - E. Gallicchio; R. M. Levy; Manish Parashar (Journal of Computational Chemistry, 2008)

Autonomic Computing Engines for Internet-Scale Applications - Manish Parashar (International Workshop on the Challenges of Large Applications in Distributed Environments (CLADE 2008), in conjunction with the 17th International Symposium on High-Performance Distributed Computing (HPDC), 2008)

Autonomic for Data/Information-Driven Science and Engineering - Manish Parashar (Invited Seminar, 2008)

Autonomics for Computational Science and Engineering - Manish Parashar (Invited Presentation. Distributed Programming Abstractions Workshop, Mardi Gras Conference 2008, 2008)

Autonomics for Grid Systems and Applications - Manish Parashar (3rd Workshop on the Use of P2P, GRID and Agents for the Development of Content Networks (UPGRADE-CN'08), in conjunction with the ACM/IEEE International Symposium on High Performance Distributed Computing (HPDC), 2008)

Autonomics for Grid Systems and Applications-Addressing Grid Complexity through Self-Management - Manish Parashar (CoreGRID Symposium, in conjunction with Euro-Par 2008, 2008)

Clustering Analysis for the Management of Self-Monitoring Device Networks - A. Quiroz; Manish Parashar; N. Gnanasambandam; N. Sharma (Proceedings of the 5th IEEE International Conference on Autonomic Computing (ICAC 2008), 2008)

Collaborative Visualization Spaces for Petascale Simulations - S Klasky; R. Barreto; A. Kahn; Manish Parashar; N. Podhorszki; S. Parker; D. Silver; M. A. Vouk (Proceedings of the 2008 International Symposium on Collaborative Technologies and Systems (CTS 2008), 2008)

Computational Support for Dynamic Parallel/Distributed Applications - Manish Parashar (Distinguished Seminar, 2008)

Coordination In Grid Environments - Z. Li; Manish Parashar (VDM Verlag, 2008)

Enabling High Speed Asynchronous Data Extraction and Transfer Using DART - C. Docan; Manish Parashar; S Klasky (Proceedings of the 17th International Symposium on High-Performance Distributed Computing (HPDC), 2008)

A Framework for Distributed Content-based Web-Services Notification in Grid Systems - A. Quiroz; Manish Parashar (Future Generation Computer Systems (FGCS) - The International Journal of Grid Computing: Theory, Methods and Applications, 2008)

GridMate: A Portable Simulation Environment for Large-Scale Adaptive Scientific Applications - X. Li; Manish Parashar (Proceedings of the 8th IEEE International Symposium on Cluster Computing and the Grid (CCGrid 2008), 2008)

In-network Data Estimation Mechanisms for Sensor-driven Scientific Applications - N. Jiang; Manish Parashar (Proceedings of the 15th IEEE International Conference on High Performance Computing (HiPC 2008), 2008)

Proceedings of the 15th IEEE International Conference on High Performance Computing - P. Sadayappan; Manish Parashar; Ramamurthy Badrinath; Viktor K. Prasanna (Springer, 2008)

Proceedings of the 15th IEEE International Conference on High Performance Computing - P. Sadayappan; Manish Parashar; Ramamurthy Badrinath; Viktor K. Prasanna (HiPC 2008, 2008)

Proceedings of the 17th IEEE International Symposium High Performance Distributed Computing - Manish Parashar; Karsten Schwan; Jon Weissman; Domenico Laforenza (HPDC 2008, 2008)

Proceedings of the 5th International Conference on Distributed Computing and Internet Technology - Manish Parashar; Sanjeev K. Aggarwal (ICDCIT 2008, 2008)

Proceedings of the International Conference on Pervasive Services - Mario Lauria; Manish Parashar; Julie McCann; Domenico Cotroneo (ICPS 2008, 2008)

Programming Support for Sensor-based Scientific Applications - N. Jiang; Manish Parashar (Proceedings of the Next Generation Software (NGS) Workshop, In conjunction with the 22nd IEEE International Parallel and Distributed Processing Symposium (IPDPS 2008), 2008)

The Role of Standardization in Future Autonomic Communication Systems - J. Strassner; J. Fleck; D. Lewis; Manish Parashar; W. Donnelly (Proceedings of the IEEE International Workshop on Engineering on Autonomic and Autonomous Systems (EASe 2008), 2008)

Scalable Computing Research-Trends, Challenges and Opportunities - Manish Parashar (2nd IEEE Doctoral Symposium, 8th IEEE International Symposium on Cluster Computing and the Grid (CCGrid 2008), 2008)

Squid: Enabling Search in DHT-based Systems - C. Schmidt; Manish Parashar (Journal of Parallel and Distributed Computing, 2008)

Addressing Challenges of Adaptivity and Scale in Parallel Scientific Applications - Manish Parashar (HPC Seminar Series, Computational Science and Engineering, College of Computing, 2007)

Analyzing the Impact of Computational Heterogeneity on Runtime Performance of Parallel Scientific Components - S. Chandra; Manish Parashar; J. Ray (Proceedings of the High Performance Computing Symposium (HPC 2007), SCS Spring Simulation Multconference (SpringSim07), 2007)

An Autonomic Data Streaming Service - V. Bhat; Manish Parashar; H. Liu; M. Khandekar; N. Kandasamy; S Klasky; S. Abdelwahed (Cluster Computing: The Journal of Networks, Software Tools, and Applications, Special Issue on Autonomic Computing, 2007)

A Computational Infrastructure for Grid-based Asynchronous Parallel Applications - Z. Li; Manish Parashar (Proceedings of the 16th International Symposium on High-Performance Distributed Computing (HPDC), 2007)

Dynamic Data-Driven Systems Approach for Simulation based Optimizations - T. Kurc; X. Zhang; Manish Parashar; H. Klie; M. F. Wheeler; U. Catalyurek; J. Saltz (Proceedings of the Workshop on Distributed Data Driven Applications and Systems, International Conference on Computational Science 2007 (ICCS 2007), 2007)

Enabling CyberPhysical Science and Engineering - Manish Parashar (Invited Presentation. Distributed Programming Abstractions Workshop, UK e-Science Center, 2007)

Enabling Scalable Parallel Implementations of Structured Adaptive Mesh Refinement Applications - S. Chandra; X. Li; T. Saif; Manish Parashar (The Journal of Supercomputing, 2007)

Experiments with In-Transit Processing for Data Intensive Grid workflows - V. Bhat; Manish Parashar; S Klasky (Proceedings of the 8th IEEE/ACM International Conference on Grid Computing (Grid 2007), 2007)

Grid-based Asynchronous Replica Exchange - Z. Li; Manish Parashar (Proceedings of the 8th IEEE/ACM International Conference on Grid Computing (Grid 2007), 2007)

GridMate: A Simulator for Adaptive Runtime Management of Dynamic Applications in Multi-site Grid Systems - X. Li; Manish Parashar (Proceedings of the 2007 International Conference on Grid Computing and Applications (GCA 2007), 2007)

High Speed Asynchronous Data Transfers on the Cray XT3 - C. Docan; Manish Parashar; S Klasky (Center for Advanced Information Processing, Rutgers University, 2007)

Hybrid Runtime Management of Space-Time Heterogeneity for Dynamic SAMR Applications - X. Li; Manish Parashar (IEEE Transactions on Parallel and Distributed Systems, 2007)

Meteor: A Middleware Infrastructure for Content-based Decoupled Interactions in Pervasive Grid Environments - Manish Parashar; C. Schmidt; N. Jiang; V. Matossian (Concurrency and Computation: Practice and Experience, 2007)

Pervasive Computational Ecosystem: Enabling Dynamic Data/Information Driven Science - Manish Parashar (Research Position Paper, 2007)

Proceedings of the 14th IEEE International Conference on High Performance Computing - Srinivas Aluru; Manish Parashar; Ramamurthy Badrinath; Viktor K. Prasanna (HiPC 2007, 2007)

An Self-Managing Wide-Area Data Streaming Service - V. Bhat; Manish Parashar; H. Liu; M. Khandekar; N. Kandasamy; S Klasky; S. Abdelwahed (Cluster Computing: The Journal of Networks, Software Tools, and Applications, Special Issue on Autonomic Computing, 2007)

When the Grid becomes Pervasive: A Vision on Pervasive Grids - Manish Parashar; J-M. Pierson (Symposium on Defining the Grid: Experiences and Future Trends, Proceedings of the 8th Hellenic European Research on Computer Mathematics & its Applications Conference (HERCMA 2007), 2007)

Accord: A Programming Framework for Autonomic Applications - H. Liu; Manish Parashar (IEEE Transactions on Systems, Man and Cybernetics, Special Issue on Engineering Autonomic Systems, 2006)

Addressing Spatiotemporal and Computational Heterogeneity for Structured Adaptive Mesh Refinement - S. Chandra; Manish Parashar (Computing and Visualization in Science, 2006)

Ant Colony Optimization and its Application to Boolean Satisfiability for Digital VLSI Circuits - R. Sethuram; Manish Parashar (Proceedings of 14th International Conference on Advanced Computing and Communication (ADCOM 2006), 2006)

Approaches to Architecture-Aware Parallel Scientific Computation - J. D. Teresco; J. E. Flaherty; S. B. Baden; J. Faik; S. Lacour; Manish Parashar; V. E. Taylor; C. Varela (Parallel Processing for Scientific Computing, 2006)

AutoMate: Enabling Autonomic Grid Applications - Manish Parashar; H. Liu; Z. Li; V. Matossian; C. Schmidt; G. Zhang; S. Hariri (Cluster Computing: The Journal of Networks, Software Tools, and Applications, 2006)

Autonomic Computing: Concepts, Infrastructure and Applications - Manish Parashar; S. Hariri (CRC Press, 2006)

The Autonomic Computing Paradigm - S. Hariri; B. Khargharia; H. Chen; J. Yang; Y. Zhang; Manish Parashar; H. Liu (Cluster Computing: The Journal of Networks, Software Tools, and Applications, 2006)

Autonomic Data Streaming for High Performance Scientific Applications - V. Bhat; Manish Parashar; N. Kandasamy (Autonomic Computing: Concepts, Infrastructure and Applications, 2006)

Autonomic Grid Computing - Concepts, Requirements, Infrastructures - Manish Parashar (Autonomic Computing: Concepts, Infrastructure and Applications, 2006)

The Center for Plasma Edge Simulation Workflow Requirements - S Klasky; B. Ludaescher; Manish Parashar (Proceedings of IEEE Workshop on Workflow and Data Flow for Scientific Applications (SciFlow 2006), in conjunction with The 22nd International Conference on Data Engineering (ICDE 2006), 2006)

Computational Support for Dynamic Parallel/Distributed Applications - Manish Parashar (IEEE Distinguished Speaker, 2006)

Data-Management in Pervasive Grid Environments - An Applications Perspective - Manish Parashar (2nd VLDB Workshop on Data Management in Grids, The 32nd International Conference on Very Large Data Bases (VLDB 2006), 2006)

A Decentralized Computational Infrastructure for Grid-Based Parallel Asynchronous Iterative Applications - Z. Li; Manish Parashar (Journal of Grid Computing, 2006)

A Decentralized Content-Based Aggregation Service for Pervasive Environments - N. Jiang; C. Schmidt; Manish Parashar (Proceedings of the IEEE International Conference on Pervasive Services (ICPS 2006), 2006)

Decentralized Data Sharing of Tissue Microarrays for Investigative Research in Oncology - W. Chen; C. Schmidt; Manish Parashar; M. Reiss; D Foran (Cancer Informatics, 2006)

Design and implementation of a Distributed Content-based Notification Broker for WS-Notification - A. Quiroz; Manish Parashar (Proceedings of the 7th IEEE International Conference on Grid Computing (Grid 2006), 2006)

Distributed Adaptive and Interactive Simulations using Structured Adaptive Mesh Refinement - Manish Parashar (13th SIAM Conference on Parallel Processing and Scientific Computing (PP06), 2006)

Driving Science and Engineering Applications by Data in Distributed Environments - J. Saltz; U. Catalyurek; T. Kurc; M. F. Wheeler; H. Klie; X. Gai; Manish Parashar; M. Peszynska; A. Sussman; S. Hastings; S. Langella; S. Narayanan; et al. (Dynamic Data Driven Applications Systems, 2006)

Dynamic Structured Partitioning for Parallel Scientific Applications with Pointwise Varying Workloads - S. Chandra; Manish Parashar; J. Ray (Proceedings of the 20th IEEE International Parallel and Distributed Processing Symposium, 2006)

Enabling Dynamic Composition and Coordination of Autonomic Applications using the Rudder Agent Framework - Z. Li; Manish Parashar (The Knowledge Engineering Review, 2006)

Enabling Efficient and Flexible Coupling of Parallel Scientific Applications - L. Zhang; Manish Parashar (Proceedings of the 20th IEEE International Parallel and Distributed Processing Symposium, 2006)

Enabling Self-Managing Applications using Model-based Online Control Strategies - V. Bhat; Manish Parashar; M. Khandekar; N. Kandasamy; S. Abdelwahed (Proceedings of the 3rd IEEE International Conference on Autonomic Computing (ICAC 2006), 2006)

Environment Sensitive Access Management for Pervasive Grid Applications - G. Zhang; Manish Parashar (Cluster Computing: The Journal of Networks, Software Tools, and Applications, 2006)

Experiments with Wide Area Data Coupling Using the Seine Framework - L. Zhang; Manish Parashar (Proceedings of the 13th IEEE International Conference on High Performance Computing (HiPC 2006), 2006)

Grid and Utility Computing: Do they really mean Pervasive Services? - Manish Parashar (Panel, The International Conference on Pervasive Services (ICPS 2006), 2006)

Grid Computing in the Digital Oil Field - V. Matossian; Manish Parashar (Harts's E&P, 2006)

Information-driven Science and the CyberInfrastructure: Opportunities for Collaboration at Rutgers - Manish Parashar (Symposium on Information Technology for Research: The Impact of the National Cyberinfrastructure, 2006)

Information-driven Science in Pervasive Grid Environments - Manish Parashar (Keynote, 2006)

An Infrastructure for Dynamic Composition of Grid Service - Z. Li; Manish Parashar (Proceedings of the 7th IEEE International Conference on Grid Computing (Grid 2006), 2006)

Models, Methods and Middleware for Grid-enabled Multiphysics Oil Reservoir Management - H. Klie; W. Bangerth; X. Gai; M. F. Wheeler; P. L. Stoffa; M. Sen; Manish Parashar; U. Catalyurek; J. Saltz; T. Kurc (Engineering with Computers, 2006)

Proceedings of the 13th IEEE International Conference on High Performance Computing - Manish Parashar; Ramamurthy Badrinath; Viktor K. Prasanna (HiPC 2006, 2006)

Proceedings of the 3rd IEEE International Conference on Autonomic COmputing (ICAC 2006) - Manish Parashar; Jeffrey Kephart; Omer F. Rana; Mazin Yousif (ICAC 2006, 2006)

A Programming System for Autonomic Self-managing Applications - H. Liu; Manish Parashar (Autonomic Computing: Concepts, Infrastructure and Applications, 2006)

Project AutoMate: Enabling Self-Managing Grid Applications - Manish Parashar; H. Liu; Z. Li; V. Matossian; C. Schmidt (Advanced Parallel and Distributed Computing, 2006)

Salsa: Scalable Asynchronous Replica Exchange for Parallel Molecular Dynamics Simulations - L. Zhang; Manish Parashar; E. Gallicchio; R. M. Levy (Proceedings of the 35th International Conference on Parallel Processing (ICPP 2006), 2006)

Seine: A Dynamic Geometry-based Shared Space Interaction Framework for Parallel Scientific Applications - L. Zhang; Manish Parashar (Concurrency and Computation: Practice and Experience, 2006)

A Self-Managing Wide-Area Data Streaming Service using Model-based Online Control - V. Bhat; Manish Parashar; M. Khandekar; N. Kandasamy; S Klasky (Proceedings of the 7th IEEE International Conference on Grid Computing (Grid 2006), 2006)

SESAME: Scalable, Environment Sensitive Access Management Engine - G. Zhang; Manish Parashar (Cluster Computing: The Journal of Networks, Software Tools, and Applications, 2006)

Towards Autonomic Control of Network Topologies - V. Matossian; Manish Parashar (Proceedings of the 1st IEEE Workshop on Modeling Autonomic Communication Environments (MACE), 2006)

Towards Dynamic Data-Driven Management of the Ruby Gulch Waste Repository - Manish Parashar; V. Matossian; H. Klie; S.G. Thomas; M. F. Wheeler; T. Kurc; J. Saltz; R. Versteeg (Proceedings of the Workshop on Distributed Data Driven Applications and Systems, International Conference on Computational Science 2006 (ICCS 2006), 2006)

Adaptive Runtime Management of Spatial and Temporal Heterogeneity for Dynamic Grid Applications - X. Li; Manish Parashar (Proceedings of the 13th High Performance Symposium (HPC 2005), SCS Spring Simulation Multiconference (SpringSim 2005), 2005)

Application of Grid-Enabled Technologies for Solving Optimization Problems in Data-Driven Reservoir Studies - Manish Parashar; H. Klie; U. Catalyurek; T. Kurc; V. Matossian; J. Saltz; M. Wheeler (Future Generation Computer Systems - The International Journal of Grid Computing: Theory, Methods and Applications, 2005)

Architecture-Aware Autonomic Adaptations within the Common Component Architecture - Manish Parashar (Minisymposium on Architecture-Aware Parallel Computation, SIAM Conference on Computational Science and Engineering (CSE05), 2005)

Autonomic Computing: An Overview - Manish Parashar; S. Hariri (Unconventional Programming Paradigms (UPP 2004), 2005)

Autonomic Computing: Concepts, Architecture, Applications - Manish Parashar (Xerox Research Lab/ISTC, 2005)

Autonomic Oil Reservoir Optimization on the Grid - V. Bhat; V. Matossian; Manish Parashar; M. Peszynska; M. Sen; P. Stoffa; M. F. Wheeler (Concurrency and Computation: Practice and Experience, 2005)

An Autonomic Reservoir Framework for the Stochastic Optimization of Well Placement - W. Bangerth; H. Klie; V. Matossian; Manish Parashar; M. F. Wheeler (Cluster Computing: The Journal of Networks, Software Tools, and Applications, 2005)

Autonomic Runtime Manager for Large Scale Adaptive Distributed Application - J. Yang; H. Chen; S. Hariri; Manish Parashar (Proceedings of the 14th IEEE International Symposium on High Performance Distributed Computing (HPDC 2005), 2005)

An Autonomic Service Architecture for Self-Managing Grid Applications - H. Liu; V. Bhat; Manish Parashar; S Klasky (Proceedings of the 6th IEEE/ACM International Workshop on Grid Computing (Grid 2005), 2005)

c - G. Zhang; Manish Parashar (Journal of Research and Practice in Information Technology (JRPIT), 2005)

Comet: A Scalable Coordination Space in Decentralized Distributed Environments - Z. Li; Manish Parashar (Proceedings of the 2nd International Workshop on Hot Topics in Peer-to-Peer Systems (HOT-P2P 2005), 2005)

Conceptual and Implementation Models for the Grid - Manish Parashar; J.C. Browne (Proceedings of the IEEE, 2005)

A Concise Introduction to Autonomic Computing - R. Sterritt; Manish Parashar; H. Tianfield; R. Unland (Journal of Advanced Engineering Informatics, Engineering Applications of Artificial Intelligence, 2005)

Cooperative Defense against DDoS Attacks - G. Zhang; Manish Parashar (Proceedings of the 2005 International Conference on Security Management (SAM 05), 2005)

Cooperative Defense against Network Attacks - G. Zhang; Manish Parashar (Proceedings of the 3rd International Workshop on Security In Information Systems (WOSIS 2005), 7th International Conference on Enterprise Information Systems (ICEIS 2005), 2005)

Data management on the fusion computational pipeline - S Klasky; M. Beck; V. Bhat; E. Feibush; B. Ludascher; Manish Parashar; A. Shoshani; D. Silver; M. Vouk (Journal of Physics: Conference Series 16, 2005)

A Decentralized Agent Framework for Dynamic Composition and Coordination for Autonomic Applications - Z. Li; Manish Parashar (Proceedings of the 16th International Workshop on Database and Expert System Applications (DEXA 2005), 3rd International Workshop on Self-Adaptive and Autonomic Computing Systems (SAACS 05), 2005)

Decentralized Information Sharing in Grid Environments - Manish Parashar (Invited Seminar, 2005)

Dispatch: Dynamic Structured Partitioning of Adaptive Applications with Computational Heterogeneity - S. Chandra; Manish Parashar; J. Ray (Technical Report Number TR-281, 2005)

Dynamic Structured Partitioning of Adaptive Applications with Computational Heterogeneity - S. Chandra; Manish Parashar; J. Ray (Center for Advanced Information Processing, Rutgers University, 2005)

Enabling Autonomic Grid Applications: Dynamic Composition, Coordination and Interaction - Z. Li; Manish Parashar (UPP 2004, 2005)

Enabling Autonomic Grid Applications: Requirements, Models and Infrastructures - Manish Parashar; Z. Li; H. Liu; V. Matossian; C. Schmidt (Self-Star 2004, Self-Star Properties in Complex Information Systems, Lecture Notes in Computer Science, 2005)

Enabling Interactive and Collaborative Oil Reservoir Simulations on the Grid - Manish Parashar; W. Lee; M. Wheeler; D. Arnold; J. Dongarra (Concurrency and Computation: Practice and Experience, 2005)

Enabling Interactive Oil Reservoir Simulations on the Grid - Manish Parashar; R. Muralidhar; W. Lee; M. Wheeler; D. Arnold; J. Dongarra (Concurrency and Computation: Practice and Experience, 2005)

Enabling Next Generation Adaptive and Interactive Computational Science - Manish Parashar (CERCS Colloquium, 2005)

Enabling Next Generation Adaptive and Interactive Computational Science/Computational Support for Dynamic Parallel/Distributed Applications - Manish Parashar (IEEE Distinguished Speaker, 2005)

Enabling Next Generation Knowledge-based Data-driven Scientific Investigation - Manish Parashar (Seminar, Department of Computer Science and Center for Computation and Technology, 2005)

Enabling Self-Management of Component Based High-Performance Scientific Applications - H. Liu; Manish Parashar (Proceedings of the 14th IEEE International Symposium on High Performance Distributed Computing (HPDC 2005), 2005)

The Foundations of Autonomic Computing - S. Hariri; Manish Parashar (Handbook of Bioinspired Algorithms and Applications, 2005)

A Framework for Rule-Based Autonomic Management of Parallel Scientific Applications - H. Liu; Manish Parashar (Proceedings of the 2nd IEEE International Conference on Autonomic Computing (ICAC 2005), 2005)

Grid Computing. An Evolving Vision - Manish Parashar; C. Lee (Proceedings of the IEEE, 2005)

Grid Computing - Introduction and Overview - Manish Parashar; C. Lee (Proceedings of the IEEE, 2005)

The Instrumented Oilfield: Towards Dynamics Data-Driven Optimization of Oil Well Placement - Manish Parashar (NSF Workshop on Distributed Data Driven Applications and Systems, International Conference on Computational Science 2005 (ICCS 2005), 2005)

Interactive and Collaborative Oil Reservoir Simulations on the Grid - Manish Parashar; W. Lee; M. Wheeler; D. Arnold; J. Dongarra (Concurrency and Computation: Practice and Experience, 2005)

Investigating Autonomic Runtime Management Strategies for SAMR Applications - S. Chandra; Manish Parashar; J. Yang; Y. Zhang; S. Hariri (International Journal of Parallel Programming, 2005)

Models, Methods and Middleware for Grid-enabled Multiphysics Oil Reservoir Management - H. Klie; W. Bangerth; X. Gai; M. F. Wheeler; P. L. Stoffa; M. Sen; Manish Parashar; U. Catalyurek; J. Saltz; T. Kurc (ICES Technical Report Number 05-34, 2005)

Proceedings of the 14th IEEE International Symposium High Performance Distributed Computing - Andrew Grimshaw; Manish Parashar; Karsten Schwan (HPDC 2005, 2005)

Proceedings of the 2005 High Performance Computing Symposium - Manish Parashar; L. Watson (HPC 2005, 2005)

Proceedings of the 2nd IEEE International Conference on Autonomic Computing - Manish Parashar; Jeffrey Kephart; Karsten Schwan; Yi-Min Wang (ICAC 2005, 2005)

Rudder: An Agent-based Infrastructure for Autonomic Composition of Grid Applications - Z. Li; Manish Parashar (Multiagent and Grid System - An International Journal, 2005)

Rule-Based Monitoring and Steering of Distributed Scientific Applications - H. Liu; Manish Parashar (International Journal of High Performance Computing and Networking (IJHPCN), 2005)

Rule-Based Visualization in the Discover Computational Steering Collaboratory - H. Liu; L. Jiang; Manish Parashar; D. Silver (2005)

Rule-based Visualization in the Discover Computational Steering Collaboratory - H. Liu; L. Jiang; Manish Parashar; D. Silver (Future Generation Computer Systems - The International Journal of Grid Computing: Theory, Methods and Applications, 2005)

Self-Optimizing of Large Scale Wild Fire Simulations - J. Yang; H. Chen; S. Hariri; Manish Parashar (Proceedings of the 5th International Conference on Computational Science (ICCS 2005), 2005)

A Simulation and Data Analysis System for Large Scale, Data-Driven Oil Reservoir Simulation Studies - T. Kurc; U. Catalyurek; X. Zhang; J. Saltz; M. Peszynska; R. Martino; M. Wheeler; A. Sussman; C. Hansen; M. Sen; R. Seifoullaev; P. Stoffa; et al. (Concurrency and Computation: Practice and Experience, 2005)

Technical Report - Sumir Chandra; Manish Parashar (Technical Report Number TR-281, 2005)

Towards Autonomic Application-Sensitive Partitioning for SAMR Applications - S. Chandra; Manish Parashar (Journal of Parallel and Distributed Computing, 2005)

Towards Dynamic Data-Driven Optimization of Oil Well Placement - Manish Parashar; V. Matossian; W. Bangerth; H. Klie; B. Rutt; T. Kurc; U. Catalyurek; J. Saltz; M. Wheeler (Proceedings of the Workshop on Distributed Data Driven Applications and Systems, International Conference on Computational Science 2005 (ICCS 2005), 2005)

Using Clustering to Address the Heterogeneity and Dynamism in Parallel SAMR Application - X. Li; Manish Parashar (Proceedings of the 12th International Conference on High Performance Computing (HiPC 2005), 2005)

A web accessible scientific workflow system for transparent and reproducible generation of information on subsurface processes from autonomously sensed data - R. Versteeg; A. Richardson; S. Thomas; B. Lu; J. Neto; M. Wheeler; T. Rowe; Manish Parashar; M. Ankeny (2005)

Active Resource Management for the Differentiated Services Environment - M. Mahajan; A. Ramanathan; Manish Parashar (International Journal of Network Management, 2004)

Analyzing the Search Characteristics of Space Filling Curve-based Indexing within Squid P2P Data Discovery System - C. Schmidt; Manish Parashar (Technical Report Number TR-276, 2004)

Application of Grid-enabled Technologies for Solving Optimization Problems in Data-Driven Reservoir Studies - Manish Parashar; H. Klie; U. Catalyurek; T. Kurc; V. Matossian; J. Saltz; M. Wheeler (Proceedings of the Workshop on Distributed Data Driven Applications and Systems, International Conference on Computational Science 2004 (ICCS 2004), 2004)

Approaches to Architecture-Aware Parallel Scientific Computation - J. D. Teresco; J. E. Flaherty; S. B. Baden; J. Faik; S. Lacour; Manish Parashar; V. E. Taylor; C. Varela (Proc. PP04: Frontiers of Scientific Computing, 2004)

Autonomic, Architecture-Aware Runtime Management of Parallel Adaptive Applications - Manish Parashar (Minisymposium on Architecture-Aware Parallel Computation, 11th SIAM Conference on Parallel Processing and Scientific Computing (PP04), 2004)

Autonomic, Architecture-Aware Runtime Management of Parallel Adaptive Applications - Manish Parashar (Minisymposium on Architecture-Aware Parallel Computation, 11th SIAM Conference on Parallel Processing and Scientific Computing (PP04), 2004)

Autonomic Computing: Foundations for a New Era in Computing - Manish Parashar (European Commission - US National Science Foundation Strategic Research Workshop on Unconventional Programming Paradigms: Challenges, Visions and Research Issues for New Programming Paradigms, 2004)

Autonomic Computing: Models, Architectures and Infrastructures - Manish Parashar (European Commission - US National Science Foundation Strategic Research Workshop on Unconventional Programming Paradigms: Challenges, Visions and Research Issues for New Programming Paradigms, 2004)

Autonomic Computing: Models, Architectures and Infrastructures - Manish Parashar; Z. Li; H. Liu; C. Schmidt; V. Matossian; N. Jiang (Proceedings of the European Commission - US National Science Foundation Strategic Research Workshop on Unconventional Programming Paradigms: Challenges, Visions and Research Issues for New Programming Paradigms, 2004)

Autonomic Proactive Runtime Partitioning Strategies for SAMR Applications - Y. Zhang; S. Chandra; J. Yang; S. Hariri; Manish Parashar (Proceedings of the NSF Next Generation Systems Program Workshop, IEEE/ACM 18th International Parallel and Distributed Processing Symposium, 2004)

Autonomic Proactive Runtime Partitioning Strategies for SAMR Applications - Y. Zhang; S. Chandra; J. Yang; S. Hariri; Manish Parashar (Proceedings of the NSF Next Generation Systems Program Workshop, IEEE/ACM 18th International Parallel and Distributed Processing Symposium, 2004)

An Autonomic Reservoir Framework - Manish Parashar (Minisymposium on Reservoir Simulation in the 21st Century, 2004 SIAM Annual Meeting (AN 2004), 2004)

An Autonomic Reservoir Framework - Manish Parashar (Minisymposium on Reservoir Simulation in the 21st Century, 2004)

An Autonomic Reservoir Framework for the Stochastic Optimization of Well Placement - V. Matossian; Manish Parashar; W. Bangerth; H. Klie; M. F. Wheeler (Cluster Computing: The Journal of Networks, Software Tools, and Applications, 2004)

A Component-based Programming Framework for Autonomic Applications - H. Liu; Manish Parashar; S. Hariri (Proceedings of the 1st IEEE International Conference on Autonomic Computing (ICAC-04), 2004)

Content-based Middleware for Decoupled Interactions in Pervasive Envionments - N. Jiang; C. Schmidt; V. Matossian; Manish Parashar (Technical Report Number-252, 2004)

Content-based Middleware for Sensor-based Pervasive Environments - C. Schmidt; Manish Parashar (Panasonic Digital Networking Laboratory, 2004)

Context-aware Dynamic Access Control for Pervasive Applications - G. Zhang; Manish Parashar (Proceedings of the Communication Networks and Distributed Systems Modeling and Simulation Conference (CNDS 2004), 2004 Western MultiConference (WMC), 2004)

Cooperative Mechanism against DDoS Attacks - G. Zhang; Manish Parashar (Proceedings of the IEEE International Conference on Information and Computer Science (ICICS 2004), 2004)

Distributed Shared Memory Tools - S. Chandra; Manish Parashar (Tool and Environments for Parallel and Distributed Computing, 2004)

A Dynamic Geometry-Based Shared Space Interaction Framework for Parallel Scientific Applications - L. Zhang; Manish Parashar (Proceedings of the 11th International Conference on High Performance Computing (HiPC 2004), 2004)

Enabling Applications in Sensor-Based Pervasive Environments - N. Jiang; Manish Parashar (Proceedings of BROADNETS 2004: Workshop on Broadband Advanced Sensor Networks (BaseNets 2004), 2004)

Enabling Autonomic Self-Managing Grid Applications - Z. Li; H. Liu; Manish Parashar (Self-Properties in Complex Information Systems, 2004)

Enabling Flexible Queries with Guarantees in P2P Systems - C. Schmidt; Manish Parashar (IEEE Internet Computing, 2004)

Engineering A Peer-to-Peer Collaboratory for Tissue Microarray Research - C. Schmidt; Manish Parashar; W. Chen; D Foran (Proceedings of the 2nd International Workshop on Challenges of Large Applications in Distributed Environments CLADE 2004, 2004)

Engineering an Autonomic Partitioning Framework for Grid-based SAMR Applications - S. Chandra; X. Li; Manish Parashar (High Performance Scientific and Engineering Computing: Hardware/Software Support, 2004)

Grid Computing: An Evolving Vision - Manish Parashar (Science on Saturdays, 2004)

Grid Computing: An Evolving Vision - Manish Parashar (Avaya Labs Research, 2004)

Hierarchical Partitioning Techniques for Structured Adaptive Mesh Refinement Applications - X. Li; Manish Parashar (Journal of Supercomputing, 2004)

A High Performance Shared Information Space Model for Parallel Scientific Applications - Manish Parashar (11th International Conference on High Performance Computing (HiPC 2004), 2004)

High Performance Threaded Data Streaming for Large Scale Simulations - V. Bhat; S Klasky; S. Atchley; M. Beck; D. McCune; Manish Parashar (Proceedings of the 5th International Workshop on Grid Computing (Grid 2004), 2004)

A Middleware Substrate for Integrating Services on the Grid - V. Bhat; Manish Parashar (Journal of Supercomputing, 2004)

Multivariate Statistical Online Analysis for Self Protection against Network Attacks - G. Qu; S. Hariri; X. Zhu; J Jin; M. Yousif; Manish Parashar (Proceedings of the IEEE International Conference on Information and Computer Science (ICICS 2004), 2004)

Online Monitoring and Analysis for Self-Protection against Network Attacks - G. Qu; S. Hariri; S. Jangiti; J. Rudraraju; S. Oh; S. Fayssal; G. Zhang; Manish Parashar (Proceedings of 1st IEEE International Conference on Autonomic Computing (ICAC-04), 2004)

Opportunistic Applications in Pervasive Environments - N. Jiang; C. Schmidt; V. Matossian; Manish Parashar (1st IEEE/ACM International Conference on Pervasive Services (ICPS 2004), 2004)

Opportunistic Applications in Pervasive Environments - Manish Parashar (1st IEEE/ACM International Conference on Pervasive Services (ICPS 2004), 2004)

Parallel and Distributed Computing: Approaches, Issues, and Challenges - S. Hairi; Manish Parashar (Tool and Environments for Parallel and Distributed Computing, 2004)

Parallel Well Location Optimization using Stochastic Algorithms on the Grid - V. Matossian; Manish Parashar; W. Bangerth; H. Klie; M. F. Wheeler (Proceedings of the 9th European Conference on the Mathematics of Oil Recovery - ECMOR IX, 2004)

Peer to Peer Information Storage and Discovery Systems - C. Schmidt; Manish Parashar (Peer-to-Peer Computing: Evolution of a Disruptive Technology, 2004)

A Peer-to-Peer Approach to Web Service Discovery - C. Schmidt; Manish Parashar (World Wide Web Journal, 2004)

Proceedings of the 1st IEEE International Conference on Autonomic Computing - Jeffrey Kephart; Manish Parashar; R. Das; V. Sunderam (ICAC 2004, 2004)

Proceedings of the 2nd International Workshop on the Challenges of Large Applications in Distributed Environments - Manish Parashar; Ray Bair (CLADE 2004, 2004)

Project METEOR: A Content-based Middleware for Decoupled Interactions in Pervasive Environments - N. Jiang; C. Schmidt; V. Matossian; Manish Parashar (Wireless Information Network Laboratory (WINLAB), Rutgers University, 2004)

Rudder: A Rule-based Multi-agent Infrastructure for Supporting Autonomic Grid Applications - Z. Li; Manish Parashar (1st IEEE International Conference on Autonomic Computing (ICAC-04), 2004)

Rule-based Visualization in a Computational Steering Collaboratory - L. Jiang; H. Liu; Manish Parashar; D. Silver (Proceedings of the International Workshop on Programming Paradigms for Grid and Metacomputing Systems, International Conference on Computational Science 2004 (ICCS 2004), 2004)

A Simulation Framework for Evaluating the Runtime Characteristics of Structured Adaptive Mesh Refinement Applications - S. Chandra; Manish Parashar (Technical Report Number TR-275, 2004)

Software Development for Parallel and Distributed Computing - S. Hairi; Manish Parashar (Tool and Environments for Parallel and Distributed Computing, 2004)

Understanding the Behavior and Performance of Non-blocking Communications in MPI - T. Saif; Manish Parashar (Proceedings of the 9th International Euro-Par Conference (Euro-Par 2004), 2004)

Using a Jini based Desktop Grid for Test Vector Compaction and a Refined Economic Model - T. Raja; Manish Parashar (Poster Publication, 4th IEEE/ACM International Symposium on Cluster Computing and the Grid (CCGrid2004), 2004)

AutoMate: Enabling Autonomic Applications - Manish Parashar (IBM Visit, 2003)

AutoMate: Enabling Autonomic Applications on the Grid - M. Agarwal; V. Bhat; Z. Li; H. Liu; B. Khargharia; V. Matossian; V. Putty; C. Schmidt; G. Zhang; S. Hariri; Manish Parashar (Proceedings of the Autonomic Computing Workshop, 5th Annual International Active Middleware Services Workshop (AMS2003), 2003)

AutoMate: Enabling Autonomic Applications on the Grid - Manish Parashar (Autonomic Computing Workshop, 5th Annual International Active Middleware Services Workshop (AMS2003), 2003)

AutoMate: Enabling Autonomic Grid Applications - M. Agarwal; V. Bhat; Z. Li; H. Liu; V. Matossian; V. Putty; C. Schmidt; G. Zhang; Manish Parashar (Technical Report Number TR-269, 2003)

Autonomic and Interactive Data-Driven Simulations using Discover - Manish Agarwal; V. Bhat; V. Matossian; Manish Parashar (Minisymposium on Electronic Fields of the Future: Mathematical and Computational Challenges, 2003)

Autonomic Applications for Pervasive Environments - Manish Parashar (Technical Presentation, 2003)

Autonomic Computational Science and Engineering (Autonomic Computing - An Applications Perspective) - Manish Parashar (Workshop on Emerging and Future Computing Paradigms and their Impact on the Research, Training and Design Environments of the Aerospace Workforce, 2003)

Autonomic Computational Science and Engineering (Autonomic Computing : An Applications Perspective) - Manish Parashar (Workshop on Emerging and Future Computing Paradigms and their Impact on the Research, Training and Design Environments of the Aerospace Workforce, 2003)

Autonomic Computing and Subsurface Modeling and Simulations - Manish Parashar (Industrial Affiliates Workshop, Center for Subsurface Modeling, ICES, 2003)

Autonomic Computing (Proceedings of the 5th International Workshop on Active Middleware Services) - Manish Parashar; Salim Hariri; C. Raghavendra (IEEE, 2003)

Autonomic Optimization of an Oil Reservoir using Decentralized Services - V. Matossian; Manish Parashar (Proceedings of the 1st International Workshop on Heterogeneous and Adaptive Computing - Challenges for Large Applications in Distributed Environments (CLADE 2003), 2003)

Autonomic Optimization of an Oil Reservoir using Decentralized Services - V. Matossian; Manish Parashar (Proceedings of the 1st International Workshop on Heterogeneous and Adaptive Computing- Challenges for Large Applications in Distributed Environments (CLADE 2003), 2003)

Computational Support for Adaptive Parallel/Distributed Applications - Manish Parashar (Workshop on Adaptive Parallel Computing, 2003)

Computational Support for Adaptive Parallel/Distributed Applications - Manish Parashar (Workshop on Adaptive Parallel Computing, Hohenwart Forum, 2003)

Controlling Unresponsive Connections in an Active Network Architecture - N. Prabhavalkar; Manish Parashar (International Journal of Network Management, 2003)

A Dimension Reducing Indexing Scheme for Guaranteed Keyword Searches in Peer-to-Peer Storage System - C. Schmidt; Manish Parashar (23rd International Conference on Distributed Computing Systems, 2003)

DIOS++: A Framework for Rule-Based Autonomic Management of Distributed Scientific Applications - H. Liu; Manish Parashar (Proceedings of the 9th International Euro-Par Conference (Euro-Par 2003), 2003)

DISCOVER: A Computational Collaboratory for Interactive Grid Applications - V. Mann; Manish Parashar (Grid Computing: Making the Global Infrastructure a Reality, 2003)

Discover Middleware Substrate for Integrating Services on the Grid - V. Bhat; Manish Parashar (Proceedings of the 10th International Conference on High Performance Computing (HiPC 2003), 2003)

A Distributed Object Infrastructure for Interaction and Steering - R. Muralidhar; Manish Parashar (Concurrency and Computation: Practice and Experience, 2003)

Dynamic Context-aware Access Control for Grid Applications - G. Zhang; Manish Parashar (Proceedings of the 4th International Workshop on Grid Computing (Grid 2003), 2003)

Dynamic Load Partitioning Strategies for Managing Data of Space and Time Heterogeneity in Parallel SAMR Applications - X. Li; Manish Parashar (Proceedings of 9th International Euro-Par Conference (Euro-Par 2003), 2003)

Enabling Autonomic Applications on the ORBIT Testbed - Manish Parashar (Technical Presentation, WINLAB IAB Meeting, 2003)

Enabling Autonomic Compositions in Grid Environments - M. Agarwal; Manish Parashar (Proceedings of the 4th International Workshop on Grid Computing (Grid 2003), 2003)

Enabling Interactive and Collaborative Computational Science on the Grid - P. Mehra; Manish Parashar (Proceedings of the 1st International Workshop on Web-based Collaboratories (Wbc-2003), IADIS International Conference WWW/Internet 2003, 2003)

Enabling Peer-to-Peer Interactions for Scientific Applications on the Grid - V. Matossian; Manish Parashar (Proceedings of the 9th International Euro-Par Conference (Euro-Par), 2003)

Flexible Information Discovery in Decentralized Distributed Systems - C. Schmidt; Manish Parashar (Proceedings of the 12th International Symposium on High Performance Distributed Computing, 2003)

A Framework for Adaptive Cluster Computing using JavaSpaces - J. Batheja; Manish Parashar (Cluster Computing: The Journal of Networks, Software Tools, and Applications, 2003)

Grid: An Autonomic Runtime System for Grid Applications - S. Hariri; Manish Parashar (12th International Symposium on High Performance Distributed Computing, 2003)

Grid Computing-An Overview (My View) - Manish Parashar (Technical Presentation, 2003)

GridARM: An Autonomic Runtime Management Framework for SAMR Applications in Grid Environments - S. Chandra; Manish Parashar; S. Hariri (New Frontiers in High-Performance Computing, Proceedings of the Autonomic Applications Workshop 10th International Conference on High Performance Computing (HiPC 2003), 2003)

GridARM: An Autonomic Runtime Management Framework for SAMR Applications in Grid Environments - Manish Parashar (Autonomic Applications Workshop, 10th International Conference on High Performance Computing (HiPC 2003), 2003)

Managing QoS for Multimedia Applications in the Differentiated Services Environment - M. Mahajan; Manish Parashar (Journal of Network and Systems Management, 2003)

A Middleware Substrate for Integrating Serivces on the Grid - V. Bhat; Manish Parashar (Journal of Supercomputing, Special Issue on Infrastructures and Applications for Cluster and Grid Computing Environments, 2003)

Page Rank Prefetching for Optimizing Access to Web Page Clusters - V. Safronov; Manish Parashar (Information Sciences Journal, 2003)

Parallel Implementation of Multiphysics Multiblock Formulations for Multiphase Flow in the Subsurface - Q. Lu; Manish Parashar; M. Peszynska; M. Wheeler (Technical Report, 2003)

A Peer to Peer Approach to Web Service Discovery - C. Schmidt; Manish Parashar (Proceedings of the 2003 International Conference on Web Service ICWS '03, 2003)

A Peer-to-Peer Approach to Web service Discovery - C. Schmidt; Manish Parashar (Technical Report Number TR-271, 2003)

A Peer-to-Peer Approach to Web service Discovery - C. Schmidt; Manish Parashar (Center for Advanced Information Processing, Rutgers University, 2003)

Proceedings of the 5th International Workshop on Active Middleware Services - Manish Parashar; Salim Hariri; C. Raghavendra (IEEE, 2003)

Project AutoMate: Autonomic Computational Science and Engineering on the Grid - Manish Parashar (CAIP Update, Center for Advanced Information Processing, Rutgers University, 2003)

Project AutoMate: Autonomic Computational Science and Engineering on the Grid - Manish Parashar (Center for Advanced Information Processing, Rutgers University, 2003)

Project AutoMate: Enabling Dynamic Data-Driven Applications and Systems - Manish Parashar (DDDAS Panel, 17th ACM/SIGARCH Annual International Conference on Supercomputing, 2003)

Real Time Feature Extraction and Tracking in a Computational Steering Environment - J. Chen; D. Silver; Manish Parashar (Proceedings of the High Performance Computing Symposium (HPC2003), 2003)

Scalable Keyword Searches with Guarantees in Peer-to-Peer Storage System - C. Schmidtt; Manish Parashar (Technical Report Number TR-266, 2003)

Self Adapting, Self Optimizing Runtime Management of Grid Applications using PRAGMA - H. Zhu; Manish Parashar; J. Yang; Y. Zhang; S. Rao; S. Hariri (Proceedings of the NSF Next Generation Systems Program Workshop, IEEE/ACM 17th International Parallel and Distributed Processing Symposium, 2003)

Self-Adapting, Self-Optimizing Runtime Management of Grid Applications using PRAGMA - H. Zhu; Manish Parashar; J. Yang; Y. Zhang; S. Rao; S. Hariri (Proceedings of the NSF Next Generation Systems Program Workshop, IEEE/ACM 17th. International Parallel and Distributed Processing Symposium, 2003)

Self-Adapting, Self-Optimizing Runtime Management of Grid Applications using PRAGMA - Manish Parashar (NSF Next Generation Systems Program Workshop, IEEE/ACM International Parallel and Distributed Processing Symposium, 2003)

SQUID: A Decentralized Discovery Service - C. Schmidt; Manish Parashar (CAIP Update, 2003)

Towards Autonomic Simulations on the Grid - Manish Parashar (Seminar, 2003)

vGrid: A Framework for Building Autonomic Applications - B. Khargharia; S. Hariri; Manish Parashar (CLADE '03: Proceedings of the 1st International Workshop on Challenges of Large Applications in Distributed Environments, 2003)

vGrid: A Framework for Development and Execution of Autonomic Grid Applications - B. Khargharia; S. Hariri; B. Kim; M. Zhang; P. Vadlamani; Manish Parashar (New Frontiers in High-Performance Computing, Proceedings of the Autonomic Applications Workshop, 10th International Conference on High Performance Computing (HiPC 2003), 2003)

Adaptive QoS Management for Collaboration in Heterogeneous Environments - R. Chowdhary; P. Bhandarkar; Manish Parashar (Proceedings of the 16th. International Parallel and Distributed Computing Symposium (IEEE, ACM), 11th. Heterogeneous Computing Workshop, 2002)

Adaptive Runtime Management of SAMR Applications - S. Chandra; S. Sinha; Manish Parashar; Y. Zhang; Y. Yang; S. Hariri (Proceedings of the 9th International Conference on High Performance Computing (HiPC 2002), 2002)

Adaptive System-Sensitive Partitioning of AMR Applications on Heterogeneous Clusters - S. Sinha; Manish Parashar (Cluster Computing: The Journal of Networks, Software Tools, and Applications, 2002)

Application Sensitive Performance Management for SAMR Applications - S. Chandra; Manish Parashar (Research poster at ASCI/ASAP Research Review, DOE ASCI/ASAP Center of Excellence, 2002)

An Application-Centric Characterization of Domain-Based Inverse Space-Filling Curve Partitioners for Parallel SAMR Applications - J. Steensland; S. Chandra; Manish Parashar (IEEE Transactions on Parallel and Distributed Systems, 2002)

An Application-Centric Characterization of Domain-Based SFC Partitioners for Parallel SAMR - J. Steensland; S. Chandra; Manish Parashar (IEEE Transactions on Parallel and Distributed Systems, 2002)

ARMaDA: An Adaptive Application-Sensitive Partitioning Framework for SAMR Applications - S. Chandra; Manish Parashar (Proceedings of the 14th IASTED International Conference on Parallel and Distributed Computing and Systems (PDCS 2002), 2002)

A CORBA Commodity Grid Kit - Manish Parashar; G. von Laszewski; S. Verma; J. Gawor; K. Keahey; N. Rehn (Concurrency and Computation: Practice and Experience, 2002)

Engineering an Interoperable Computational Collaboratory on the Grid - V. Mann; Manish Parashar (Concurrency and Computation: Practice and Experience, 2002)

A Framework for Enabling Collaboration over Heterogeneous Networks - P. Bhandarkar; Manish Parashar (Proceedings of the 4th Workshop on Information and Computer Science, 2002)

Grid Computing-GRID 2012 - Manish Parashar (Springer, 2002)

Hierarchical Partitioning Techniques for Structured Adaptive Mesh Refinement (SAMR) Applications - X. Li; S. Ramanathan; Manish Parashar (Proceedings of the 2002 International Conference on Parallel Processing (ICPP 2002), 4th Workshop on High Performance Scientific and Engineering Computing Applications (HPSECA-02), 2002)

Integrating Grid Services using the DISCOVER Middleware - V. Bhat; Manish Parashar (Technical Report Number TR-268, 2002)

Latency Performance of SOAP Implementations - D. Davis; Manish Parashar (Proceedings of the 2nd IEEE/ACM Symposium on Cluster Computing and the Grid, Workshop on Global and Peer-to-Peer on Large Scale Distributed Systems, 2002)

Managing QoS for Multimedia Applications in a Differentiated Services Environment - M. Mahajan; Manish Parashar (Proceedings of the 4th Annual International Workshop on Active Middleware Services, 2002)

Optimizing Web Servers Using Page Rank Prefetching for Clustered Accesses - V. Safronov; Manish Parashar (World Wide Web, Internet and Web Information Systems, 2002)

PRAGMA: An Infrastructure for Runtime Management of Grid Applications - Manish Parashar; S. Hariri (Proceedings of the NSF Next Generation Systems Program Workshop, IEEE/ACM 16th International Parallel and Distributed Processing Symposium, 2002)

Scalable Keyword Searches with Guarantees in Peer-to-Peer Storage Systems - C. Schmidt; Manish Parashar (Technical Report Number TR-266, 2002)

A Software Design Model for Parallel Applications on Heterogeneous System - M. Dwivedula; S. Hariri; Manish Parashar (Proceedings of the 16th International Parallel and Distributed Computing Symposium (IEEE, ACM), 11th Heterogeneous Computing Workshop, 2002)

A Study of Discovery Mechanisms For Peer-to-Peer Applications - M. Kelaskar; V. Matossian; P. Mehra; D. Paul; A. Vaidhyanathan; Manish Parashar (Proceedings of the 2nd IEEE/ACM International Symposium on Cluster Computing and the Grid Workshop on Global and Peer-to-Peer on Large Scale Distributed Systems, 2002)

Using Page Rank Prefetching for Clustered Web Accesses - V. Safronov; Manish Parashar (Proceedings of the 4th Workshop on Information and Computer Science, 2002)

Active Resource Management for the Differentiated Services Environment - A. Ramanathan; Manish Parashar (Proceedings of the 3rd Annual International Workshop on Active Middleware Services, 2001)

Active Resource Management for the Differentiated Services Environment - A. Ramanathan; Manish Parashar (Proceedings of the International Conference on Internet Computing (IC 2001), 2001)

Adaptive Application Sensitive Partitioning Strategies for SAMR Applications - S. Chandra; J. Steensland; Manish Parashar (Poster publication at IEEE/ACM Supercomputing 2001, 2001)

Adaptive Cluster Computing using JavaSpaces - J. Batheja; Manish Parashar (Proceedings of the 3rd IEEE International Conference on Cluster Computing, 2001)

Adaptive QoS Management for Collaboration in Heterogeneous Environments - Manish Parashar (2001)

Adaptive Runtime Partitioning of AMR Applications on Heterogeneous Clusters - S. Sinha; Manish Parashar (Proceedings of the 3rd IEEE International Conference on Cluster Computing, 2001)

A Computational Collaboratory for Interactive Reservoir Simulations - Manish Parashar (ndustrial Affiliates Workshop, Center for Subsurface Modeling, 2001)

CORBA Commodity Grid Toolkit - Manish Parashar (Community Practice Paper, 1st Global Grid Forum, Amsterdam, Netherlands, 2001)

Design and Implementation of a CORBA Commodity Grid Kit - S. Verma; Manish Parashar; J. Gawor; G. von Laszewski (Proceedings of the 2nd International Workshop on Grid Computing, 2001)

DISCOVER: An Environment for Web-based Interaction and Steering of High-Performance Scientific Applications - V. Mann; V. Matossian; R. Muralidhar; Manish Parashar (Concurrency and Computation: Practice and Experience, 2001)

DISCOVER: An Interactive Computational Collaboratory for Grid Applications - Manish Parashar (Community Practice Paper, 1st Global Grid Forum, 2001)

DISCOVER: An Interactive Computational Collaboratory for Grid Applications - Manish Parashar (Community Practice Paper, 1st Global Grid Forum, Amsterdam, Netherlands, 2001)

The DISCOVER Computational Collaboratory for Computational Epidemiology - Manish Parashar (CAIP Symposium on Homeland Security, 2001)

A Distributed Object Infrastructure for Interaction and Steering - R. Muralidhar; Manish Parashar (Proceedings of the 7th International Euro-Par Conference (Euro-Par 2001), 2001)

Engineering a Computational Collaboratory on the Grid: An Overview of the DISCOVER Project - Manish Parashar (Colloquium, Information Technology Center, 2001)

Engineering a Computational Collaboratory on the Grid: An Overview of the DISCOVER Project - Manish Parashar (Seminar, 2001)

Engineering a Distributed Computational Collaboratory - S. Kaur; V. Mann; V. Matossian; R. Muralidhar; Manish Parashar (Proceeding of the 34th Hawaii Conference on System Sciences, 2001)

Engineering the DISCOVER Computational Collaboratory - Manish Parashar (The Applied Software System Laboratory, Rutgers, 2001)

An Evaluation of Partitioners for Parallel SAMR Applications - S. Chandra; Manish Parashar (Proceedings of the 7th International Euro-Par Conference (Euro-Par 2001), 2001)

Event Services for Grid Computing Environments - Manish Parashar (Community Practice Paper, 2nd Global Grid Forum, VA, USA, July 2001. (Archived at www.computingportals.org), 2001)

An Experimental Study of Adaptive Application Sensitive Partitioning Strategies for SAMR Applications - S. Chandra; J. Steensland; Manish Parashar; J. Cummings (Proceedings of the 2nd LACSI (Los Alamos Computer Science Institute) Symposium 2001, 2001)

A Framework for Opportunistic Cluster Computing using JavaSpaces - J. Batheja; Manish Parashar (Proceedings of the 9th International Conference on High Performance Computing and Networking (HPCN 2001), Workshop on Java in High Performance Computing, 2001)

Middleware Support for Global Access to Integrated Computational Collaboratories - V. Mann; Manish Parashar (Proceedings of 10th IEEE International Symposium on High Performance Distributed Computing, 2001)

Middleware Support for Global Access to Integrated Computational Collaboratories - V. Mann; Manish Parashar (Proceedings of 10th IEEE International Symposium on High Performance Distributed Computing, 2001)

Multimedia Content Adaptation for QoS Management over Heterogeneous Networks - N. Shaha; A. Dessai; Manish Parashar (Proceedings of the International Conference on Internet Computing (IC 2001), 2001)

A Multi-Threaded Communication Engine for Distributed Adaptive Applications - S. Ramanathan; Manish Parashar (Proceedings of the 2001 International Conference on Parallel and Distributed Processing Techniques and Applications (PDPTA 2001), 2001)

M-YESSIR: A Low Latency Reservation Protocol for Mobile-IP Networks - H. Khosravi; D. Reininger; M. Ott; Manish Parashar (Proceedings of Advanced Internet Charging and QoS Technology (ICQT 01) Workshop WS3 of Informatik, 2001)

Parallel Computing in Computational Fluid Dynamics - R. Henderson; D. Meiron; Manish Parashar; R. Samtaney (CRPC Handbook of Parallel Computing, 2001)

Parallel Computing in Environment and Energy - M. F. Wheeler; W. Lee; C. N. Dawson; D. C. Arnold; T. Kurc; Manish Parashar (CRPC Handbook of Parallel Computing, 2001)

System Sensitive Runtime Management of Adaptive Applications - S. Sinha; Manish Parashar (Abstract/Presentation at the 10th SIAM Conference on Parallel Processing for Scientific Computing, 2001)

System Sensitive Runtime Management of Adaptive Applications on Heterogeneous Environments - S. Sinha; Manish Parashar (Proceedings of the 15th International Parallel and Distributed Computing Symposium (IEEE, ACM), 10th Heterogeneous Computing Workshop, 2001)

Adaptive Distribution of Dynamic Grid Hierarchies - S. Ramanathan; Manish Parashar (Abstract/Presentation at the special session on Parallel Adaptive Computations, p and hp Finite Element Method: Mathematics and Engineering Practice, 2000)

An Architecture for Web-based Interaction and Steering of Adaptive Parallel/Distributed Applications - R. Muralidhar; S. Kaur; Manish Parashar (Proceedings of the 6th International Euro-Par Conference (Euro-Par 2000), 2000)

Characterization of Domain-based Partitioners for Parallel SAMR Applications - J. Steensland; M. Thune; S. Chandra; Manish Parashar (Proceedings of the IASTED International Conference on Parallel and Distributed Computing Systems, 2000)

DISCOVER: A Virtual Interactive Computational Collaboratory - M. Dhillon; S. Kaur; V. Mann; V. Matossian; R. Muralidhar; A. Swaminathan; S. Verma; Manish Parashar (Center for Advanced Information Processing, Rutgers University, 2000)

An Environment for Web-based Interaction and Steering of High- Performance Scientific Applications - S. Kaur; R. Muralidhar; Manish Parashar (ACM Java Grande Conference, 2000)

Interpretive Performance Prediction for Parallel Application Development - Manish Parashar; S. Hariri (Journal of Parallel and Distributed Computing, 2000)

LGC: An Active Congestion Control Mechanism - N. Prabhavalkar; Manish Parashar; P. Agrawal (Active Middleware Services, 2000)

An Object Infrastructure for Computational Steering of Distributed Simulations - R. Muralidhar; Manish Parashar (Proceedings of the Ninth IEEE International Symposium on High-Performance Distributed Computing (HPDC 2000), 2000)

Scalability of Irregular Adaptive Mesh Refinement - Manish Parashar (Scalability Workshop, ACM International Conference on Supercomputing, 2000)

Systems Engineering for High Performance Computing Software: The HDDA/DAGH Infrastructure for Implementation of Parallel Structured Adaptive Mesh Refinement - Manish Parashar; J.C. Browne (IMA Volume 117: Structured Adaptive Mesh Refinement (SAMR) Grid Methods, 2000)

Using Java Interaction Proxies for Web-based Steering of Distributed Simulations - R. Muralidhar; Manish Parashar (Proceedings of the First Conference on Distributed Objects in Computational Science, 2000)

An Application-Centric Characterization of Distribution Techniques for Dynamic Adaptive Grid Hierarchies - S. Bhavsar; M. Shee; Manish Parashar (1999 International Conference on Parallel and Distributed Processing Techniques and Applications (PDPTA 99), 1999)

A Characterization of Distribution Techniques for Dynamic Adaptive Grid Hierarchies - S. Bhavsar; M. Shee; Manish Parashar (5th U.S. National Congress on Computational Mechanics (USACM), 1999)

Characterizing the Performance of Dynamic Distribution and Load-Balancing Techniques for Adaptive Grid Hierarchies - S. Bhavsar; M. Shee; Manish Parashar (IASTED International Conference on Parallel and Distributed Computing and Systems, 1999)

Adaptive Mesh Refinement using DAGH: A Tutorial - Manish Parashar (Department of Electrical and Computer Engineering, Rutgers University, 1998)

Architectures and Techniques for Using High Performance Computers to Support Workstation Based DII COE Applications - S. Bhavsar; W. Hu; Manish Parashar (Proceedings of the DOD HPCMP Users Group Conference, 1998)

An Environment for Parallel Multi-Block, Multi-Resolution Reservoir Simulations - Manish Parashar; I. Yotov (Proceedings of the 11th International Conference on Parallel and Distributed Computing Systems (PDCS 98), 1998)

HDDA: A Distributed Dynamics Data Structure for Parallel Adaptive Computations - Manish Parashar (Center for Advanced Information Processing, Rutgers University, 1998)

Integrated Data-Management for Computational Steering - Manish Parashar; J.C. Browne (Proceedings of 31st Annual Hawaii International Conference on System Sciences, 1998)

Integrated Data-Management for Computational Steering - Manish Parashar (IEEE Conference on Information Technology, 1998)

Replicating Distributed Events for Real-Time Collaboration - P. Bhandarkar; Manish Parashar (Department of Electrical and Computer Engineering, Rutgers University, 1998)

Semantic Communication for Distributed Information Coordination - P. Bhandarkar; Manish Parashar (Proceedings of the IEEE Conference on Information Technology, 1998)

Building Programming Environments for Parallel Adaptive Finite Difference Applications - Manish Parashar; P. Walker (Albert-Einstein Institute, Max Plank Institue, Potsdam, Germany, 1997)

A Common Data Management Infrastructure for Parallel Adaptive Algorithms for PDE Solutions - Manish Parashar; J.C. Browne; C. Edwards; K. Klimkowsky (Proceeding of Supercomputing '97, 1997)

A Computational Infrastructure for Parallel Adaptive Methods - Manish Parashar; J.C. Browne; C. Edwards; K. Klimkowsky (Symposium on Parallel Adaptive Method, 4th U.S. Congress on Computational Mechanics, 1997)

Interpretive Performance Prediction for High Performance Application Development - Manish Parashar; S. Hariri (Proceedings of the 30th Annual Hawaii International Conference on System Sciences, 1997)

A New Generation EOS Compositional Reservoir Simulator: Formulation and Discretization - P. Wang; I. Yotov; M. Wheeler; T. Arbogast; C. Dawson; Manish Parashar; K. Sepehrnoori (Proceedings of the Society of Petroleum Engineers, Reservoir Simulation Symposium, 1997)

A New Generation EOS Compositional Reservoir Simulator: Framework and Multiprocessing - Manish Parashar; J. A. Wheeler; G. Pope; K. Wang; P. Wang (Proceedings of the Society of Petroleum Engineers, Reservoir Simulation Symposium, 1997)

Systems Engineering Issues in the Implementation of an Infrastructure for Parallel Structured Adaptive Meshes - Manish Parashar; J.C. Browne (Proceedings of Workshop on Structured Adaptive Mesh Refinement Grid Methods, SIAM Conference on Parallel Processing for Scientific Computing, 1997)

Compile-Time Performance Interpretation of HPF/Fortran 90D - Manish Parashar; S. Hariri (IEEE Parallel and Distributed Technology, 1996)

Object-Oriented Programming Abstractions for Parallel Adaptive Mesh-Refinement - Manish Parashar; J.C. Browne (Parallel Object-Oriented Methods and Applications (POOMA), 1996)

On Partitioning Dynamic Adaptive Grid Hierarchies - Manish Parashar; J.C. Browne (Proceedings of the 29th Annual Hawaii International Conference on System Sciences, 1996)

DAGH Users Guide - Manish Parashar (TICAM, University of Texas at Austin, 1995)

Distributed Dynamic Data-Structures for Parallel Adaptive Mesh-Refinement - Manish Parashar; J.C. Browne (Proceedings of the International Conference for High Performance Computing, 1995)

An Infrastructure for Parallel Adaptive Mesh-Refinement Techniques - Manish Parashar; J.C. Browne (TICAM, University of Texas at Austin, 1995)

Parallel Multigrid on Adaptive Mesh Refinement Hierarchies - Manish Parashar; M. W. Choptuik; S Klasky (Center for Relativity, University of Texas at Austin, 1995)

Programming Abstraction for Parallel Adaptive Mesh-Refinement - Manish Parashar; J.C. Browne (TICAM, University of Texas at Austin, 1995)

Software Tool Evaluation Methodology - S. Hariri; Manish Parashar; S. Park; R. Reddy; M. Subramanium; J. Yadav; G. C. Fox (Proceedings of the International Conference on Distributed Computing Systems, 1995)

A Communication System for High Performance Distributed Computing - S. Hariri; J. B. Park; Manish Parashar; G. C. Fox (Concurrency and Computation: Practice and Experience, 1994)

Design of an Application Development Toolkit for HPF/Fortran 90D - Manish Parashar; S. Hariri; T. Haupt; G. C. Fox (Proceedings of the International Workshop on Parallel Processing, 1994)

Interpreting the Performance of HPF/Fortran 90D - Manish Parashar; S. Hariri; T. Haupt; G. C. Fox (Proceedings of Supercomputing `94 (ACM Sigarch and IEEE Computer Society), 1994)

Parallel Software Benchmarks for High Performance BMC3/IS Systems - B. Thiagarajan; D. Jadav; Manish Parashar; S. Hariri; G. C. Fox (Technical Report RL-TR-94-77, 1994)

A Study of Software Development for High Performance Computing - Manish Parashar; S. Hariri; T. Haupt; G. C. Fox (Programming Environments for Massively Parallel Distributed Systems, 1994)

A Survey of Software Systems Supporting Parallel/Distributed Grids - Manish Parashar (TICAM, University of Texas at Austin, 1994)

An Integrated Software Development Model for Heterogeneous High Performance Computing - Manish Parashar; S. Hariri (NPAC Technical Report SCCS-453, 1993)

An Intelligent Performance Optimizer for Network-Based Distributed Systems - Manish Parashar; S. Hariri (NPAC Technical Report SCCS-418, 1993)

An Interpretive Framework for Application Performance Prediction - Manish Parashar; S. Hariri; T. Haupt; G. C. Fox (Proceedings of the 1993 International Conference On Parallel and Distributed Systems (ICPADS 1993), 1993)

A Message Passing Interface for Parallel and Distributed Computing - S. Hariri; Manish Parashar; J. B. Park; F. K. Yu; G. C. Fox (Proceedings of the 2nd International Symposium on High Performance Distributed Computing (HPDC-2), 1993)

Software and Hardware Issues for Workstation-Based Supercomputing - S. Hariri; Manish Parashar; J. B. Park (Proceedings of the 26th International Conference on System Sciences (HICSS-26), 1993)

Application Benchmark Set for Fortran D and High Performance Fortran - A. G. Mohamed; G. C. Fox; G. von Laszewski; Manish Parashar; T. Haupt; K. Mills; Y. Lu; N. Lin; N. Yeh (NPAC Technical Report SCCS-327, 1992)

A Case for Heterogeneous Network Computing - Manish Parashar; S. Hariri; J. Park; F. Yu; G. C. Fox (NPAC Technical Report SCCS-417, 1992)

An Environment for High Performance Distributed Computing - Manish Parashar; S. Hariri; J. Park; F. Yu; G. C. Fox (NPAC Technical Report, 1992)

An Expert System for Performance Management - Manish Parashar; S. Hariri; K. Jabbour (NPAC Technical Report SCCS-354, 1992)

An Expert System for Performance Management - Manish Parashar; S. Hariri; K. Jabbour (Proceedings of the 35th Midwest Symposium on Circuits and Systems, 1992)

An Expert System for Performance Management - Manish Parashar; S. Hariri; K. Jabbour (Proceedings of the 35th Midwest Symposium on Circuits and Systems, 1992)

MHiSS: A Memory Hierarchy for Stable Storage - Manish Parashar; S. Hariri (NPAC Technical Report SCCS-355, 1992)

On the Parallelization of Blocked LU Factorization Algorithms for Distributed Memory Architectures - G. von Laszewski; Manish Parashar; A. G. Mohamed; G. C. Fox (Proceedings of Supercomputing 92 (ACM Sigarch and IEEE Computer Society), 1992)

A Requirement Analysis for High Performance Distributed Computing over LAN's - Manish Parashar; S. Hariri; A. G. Mohamed; G. C. Fox (Proceedings of the 1st International Symposium on High Performance Distributed Computing (HPDC-1), 1992)

Abstractions for Distributed Applications and Systems: A Computational Science Perspective - Shantenu Jha; Daniel S. Katz; Manish Parashar; Omer Rana; Jon Weissman (Wiley Book Series)

Driving Science and Engineering Applications by Data: Dynamic Data-Driven Approaches for Simulation- Based Optimization and Decision Making - Manish Parashar; Tahsin Kurc; Mary F. Wheeler; Umit V Catalyurek; Joel Saltz (Dynamic Data Driven Applications Systems)

Exploring Automatic, Online Failure Recovery for Scientific Applications at Extreme Scales - Marc Gammell; Daniel S. Katz; Hermanth Kolla; Jacqueline Chen; Manish Parashar (Proceedings of SC’14, The ACM/IEEE International Conference for High Performance Computing, Networking Storage and Analysis)

Software Design for Passing Sarbanes Oxley in Cloud Computing - Solomon Lasluisa; Ivan Rodero; Manish Parashar; Claus-Peter Ruckemann (Integrated Information and Computing Systems For Natural, Spatial, and Social Sciences)